Fluorine-containing ether compound, lubricant for magnetic recording medium, and magnetic recording medium

JP7635726B2Active Publication Date: 2025-02-26RESONAC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021575803
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-07
Filing Date
2021-02-02
Publication Date
2025-02-26
Estimated Expiration
2041-02-02

Smart Images

  • Figure 0007635726000047
    Figure 0007635726000047
  • Figure 0007635726000001
    Figure 0007635726000001
  • Figure 0007635726000002
    Figure 0007635726000002
Patent Text Reader

Abstract

A fluorine-containing ether compound that is characterized by being represented by the following formula (1). Formula (1): R1-(O(CH2)a)b-[A]-[B]-O-CH2-R2-CH2-R3 (In formula (1), R1 is an alkyl group that may have a substituent group, or an organic group that has at least one double bond or triple bond, a is an integer from 2 to 4, and b is 0 or 1. [A] is represented by formula (2): -(OCH2CH(OH)CH2)c- (where c is 1 or 2). [B] is represented by formula (3): -(O(CH2)eCH(OH)CH2)d- (where d is 0 or 1, and e is an integer from 2 to 4). The sum of the values of c in formula (2) and d in formula (3) is 2. R2 is a perfluoropolyether chain. R3 is represented by formula (4): -(OCH2CH(OH)CH2)2-O-CH2(CH2)fOH (where f is an integer from 2 to 5).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluorine-containing ether compound suitable for use as a lubricant for magnetic recording media, a lubricant for magnetic recording media containing the same, and a magnetic recording medium. This application claims priority based on Japanese Patent Application No. 2020-020180, filed on February 7, 2020, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, with the dramatic increase in the amount of information processed via the Internet, attention has been focused on the development of recording media for storing that information. In particular, magnetic recording media, which is one type of recording media, are expected to be able to accommodate the increasing amount of information because they can be made large-capacity at low cost. In magnetic recording media, a protective layer and a lubricating layer are provided on the magnetic layer (magnetic recording layer) formed on a substrate in order to ensure the durability and reliability of the magnetic recording media. In particular, the lubricating layer disposed on the outermost surface is required to have various properties such as long-term stability, resistance to chemical substances (to prevent contamination by siloxane, etc.), wear resistance, and heat resistance.

[0003] As lubricants for magnetic recording media, lubricants containing a compound having a polar group such as a hydroxyl group at the end of a fluorine-based polymer having a repeating structure containing CF2 have been proposed so far (see, for example, Patent Documents 1 to 7). Specifically, Patent Document 1 discloses a compound having a plurality of hydroxyl groups at both terminal portions of a fluorine-based polymer, the hydroxyl groups being arranged so that the shortest distance between the hydroxyl groups is three atoms or more. Patent Document 2 discloses a fluoropolyether compound having an aromatic group at one end of a fluorine-based polymer and a hydroxyl group at the other end. Patent Document 3 discloses a compound having a perfluoropolyether main chain and an aromatic group and a hydroxyl group at the molecular terminals, the aromatic group and the hydroxyl group being bonded to different carbon atoms.

[0004] Patent Document 4 discloses a fluorine-containing ether compound having a perfluoropolyether chain. At one end of the perfluoropolyether chain, an end group containing an organic group having at least one double bond or triple bond is arranged via a divalent linking group that is linked by etheric oxygen. At the other end of the perfluoropolyether chain, an end group is arranged that contains two or three polar groups, each polar group is linked to a different carbon atom, and the carbon atoms to which the polar groups are linked are linked to each other via a linking group that contains a carbon atom to which the polar groups are not linked.

[0005] Patent Document 5 discloses a fluorine-containing ether compound having a perfluoropolyether chain. The terminal groups at both ends of the fluorine-containing ether compound are either an alkyl group which may have a substituent, an organic group having at least one double bond or triple bond, or a hydrogen atom. In addition, a linking group containing a hydroxyl group is disposed between the perfluoropolyether chain and the terminal groups at both ends.

[0006] Patent Document 6 discloses a fluorine-containing ether compound having a perfluoropolyether chain. At one end of the perfluoropolyether chain, an alkyl group that may have a substituent is arranged via a divalent linking group. At the other end of the perfluoropolyether chain, an end group is arranged, which includes two or three polar groups, each of which is bonded to a different carbon atom, and the carbon atoms to which the polar groups are bonded are bonded to each other via a linking group that includes a carbon atom to which the polar groups are not bonded.

[0007] Patent Document 7 discloses a fluorine-containing ether compound having a perfluoropolyether chain. At least one of the terminal groups of the fluorine-containing ether compound is provided with a group in which one or more hydrogen atoms of an organic group having 1 to 8 carbon atoms are substituted with a cyano group. In addition, a divalent linking group having a polar group is provided between the perfluoropolyether chain and the terminal group. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 4632144 [Patent Document 2] Patent No. 5909837 [Patent Document 3] Patent No. 5465454 [Patent Document 4] International Publication No. 2017 / 154403 [Patent Document 5] International Publication No. 2019 / 054148 [Patent Document 6] International Publication No. 2019 / 049585 [Patent Document 7] International Publication No. 2019 / 039200 Summary of the Invention [Problem to be solved by the invention]

[0009] In order to increase the recording density of a magnetic recording medium and thereby increase its capacity, it is necessary to reduce the magnetic spacing, which is the distance between the magnetic head and the magnetic layer of the magnetic recording medium. Possible methods for reducing the magnetic spacing include lowering the flying height of the magnetic head and reducing the thickness of the lubricating layer.

[0010] However, lowering the flying height of the magnetic head makes it more likely that pick-up will occur, in which the fluorine-containing ether compound in the lubricating layer adheres to the magnetic head as foreign matter (smear).

[0011] In recent years, the rotation speed of magnetic recording media has been increasing. This has led to increased susceptibility to spin-off of the lubricant layer. Spin-off is a phenomenon in which the lubricant is scattered or evaporated due to centrifugal force and heat generated by the rotation of the magnetic recording medium. It is possible to reduce the thickness of the lubricating layer by decreasing the average molecular weight of the lubricant, but in that case, spin-off becomes more likely to occur.

[0012] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a fluorine-containing ether compound that can form a lubricating layer that is less susceptible to pick-up and spin-off, regardless of the average molecular weight of the fluorine-containing ether compound in the lubricant, and that can be suitably used as a material for a lubricant for magnetic recording media. Another object of the present invention is to provide a lubricant for magnetic recording media, which contains the fluorine-containing ether compound of the present invention. Another object of the present invention is to provide a magnetic recording medium having a lubricating layer containing the fluorine-containing ether compound of the present invention. [Means for solving the problem]

[0013] The present inventors have conducted extensive research in order to solve the above problems. As a result, they discovered that by using a lubricant for magnetic recording media containing a fluorinated ether compound having a specific molecular structure, it is possible to form a lubricating layer that has good adhesion to the protective layer and can suppress pick-up and spin-off even when the molecular weight is reduced, and this led to the invention. That is, the present invention relates to the following.

[0014] [1] A fluorinated ether compound represented by the following formula (1): R 1 -(O(CH2) a ) b -[A]-[B]-O-CH2-R 2 -CH2-R 3 (1) (In formula (1), R 1 is either an alkyl group which may have a substituent, or an organic group having at least one double bond or triple bond. a is an integer of 2 to 4, and b is 0 or 1. [A] is represented by the following formula (2). In formula (2), c is 1 or 2. [B] is represented by the following formula (3). In formula (3), d is 0 or 1, and e is an integer of 2 to 4, provided that the sum of the values ​​of c in formula (2) and d in formula (3) is 2. R 2 is a perfluoropolyether chain. 3is represented by the following formula (4), where f is an integer of 2 to 5.

[0015] [ka]

[0016] [2] The fluorinated ether compound according to [1], having a number average molecular weight in the range of 1,000 to 2,300. [3] R in the above formula (1) 1 is an alkyl group having 1 to 6 carbon atoms. [4] R in the above formula (1) 1 is a substituted alkyl group having 1 to 6 carbon atoms, The fluorine-containing ether compound according to [1] or [2], wherein the substituent is a fluoro group or a cyano group. [5] R in the above formula (1) 1 is any one of an organic group having 6 to 12 carbon atoms and having an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms and having an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms. [6] R in the above formula (1) 1 is one group selected from the group consisting of a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,2,2,2,2-hexafluoroisopropyl group, a 2-cyanoethyl group, a 3-cyanopropyl group, a 4-cyanobutyl group, a phenyl group, a methoxyphenyl group, a cyanophenyl group, a phenethyl group, a thienylethyl group, an N-methylpyrazolylmethyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, a propargyl group, a 3-butynyl group, and a 4-pentynyl group.

[0017] [7] R in the above formula (1) 2is any one of the following formulae (5) to (8): -CF2O-(CF2CF2O) g -(CF2O) h -CF2- (5) (In formula (5), g and h are average degrees of polymerization, g represents 3 to 8, and h represents 3 to 8.) -CF2O-(CF2CF2O) i -CF2- (6) (In formula (6), i is the average degree of polymerization and represents 5 to 13.) -CF2CF2O-(CF2CF2CF2O) j -CF2CF2- (7) (In formula (7), j is the average degree of polymerization and represents 3 to 8.) -CF(CF3)-(OCF(CF3)CF2) k -OCF(CF3)- (8) (In formula (8), k is the average degree of polymerization and represents 3 to 8.)

[0018] [8] The fluorine-containing ether compound according to [1], wherein the compound represented by formula (1) is any of compounds represented by the following formulae (A1) to (A3), (B1) to (B3), (L1), and (M1):

[0019] [ka]

[0020] (In formula (A1), ma1 and na1 are average degrees of polymerization, ma1 represents 3 to 8, and na1 represents 3 to 8.) (In formula (A2), na2 is the average degree of polymerization and represents 5 to 13.) (In formula (A3), na3 is the average degree of polymerization and represents 3 to 8.) (In formula (B1), mb1 and nb1 are average degrees of polymerization, mb1 represents 3 to 8, and nb1 represents 3 to 8.) (In formula (B2), nb2 is the average degree of polymerization and represents 5 to 13.) (In formula (B3), nb3 is the average degree of polymerization and represents 3 to 8.) (In formula (L1), ml1 and nl1 are average degrees of polymerization, ml1 represents 3 to 8, and nl1 represents 3 to 8.) (In formula (M1), mm1 and nm1 are average degrees of polymerization, mm1 represents 3 to 8, and nm1 represents 3 to 8.)

[0021] [9] A lubricant for magnetic recording media, comprising the fluorine-containing ether compound according to any one of [1] to [8].

[10] A magnetic recording medium comprising at least a magnetic layer, a protective layer and a lubricating layer provided in that order on a substrate, the lubricating layer comprising the fluorine-containing ether compound according to any one of [1] to [8].

[11] The magnetic recording medium according to

[10] , wherein the lubricating layer has an average thickness of 0.5 nm to 2.0 nm. Effect of the Invention

[0022] The fluorine-containing ether compound of the present invention is a compound represented by the above formula (1), and is suitable as a material for a lubricant for a magnetic recording medium. The lubricant for magnetic recording media of the present invention contains the fluorine-containing ether compound of the present invention, and therefore can form a lubricating layer that has good adhesion to a protective layer and can suppress pick-up and spin-off without being affected by the average molecular weight of the fluorine-containing ether compound in the lubricant. The magnetic recording medium of the present invention has a lubricating layer that has good adhesion to the protective layer and can suppress pick-up and spin-off. [Brief description of the drawings]

[0023] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a magnetic recording medium of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In order to achieve the above object, the present inventors have focused on the relationship between the molecular structure of the fluorine-containing ether compound contained in the lubricating layer and the protective layer, and have conducted extensive research as described below. The molecular structure of the fluorine-containing ether compound contained in the lubricating layer significantly affects the film thickness and adhesion properties of the lubricating layer. Conventionally, in order to obtain a lubricating layer with good adhesion to a protective layer, a perfluoropolyether-based compound containing a hydroxyl group in the molecule (hereinafter, sometimes referred to as a "PFPE-based compound") has been used as a lubricant. However, even when the lubricating layer contains a PFPE-based compound having multiple hydroxyl groups in the molecule, there are cases in which the adhesion of the lubricating layer to the protective layer is not sufficient.

[0025] As a result of intensive research, the present inventors have found that even in a lubricating layer containing a PFPE-based compound having multiple hydroxyl groups, sufficient adhesion with the protective layer cannot be obtained unless the hydroxyl groups in the PFPE-based compound are effectively involved in bonding with the active sites on the protective layer. Furthermore, as a result of extensive research by the present inventors, it has been found that when the PFPE compound contained in the lubricating layer contains many hydroxyl groups that are not involved in bonding with the active sites on the protective layer, the following tendency occurs: That is, the lubricant is easily spin-off, in which the lubricant is reduced due to scattering and evaporation caused by centrifugal force and heat during high-speed rotation, or pick-up, in which the lubricant adheres to the magnetic head as foreign matter (smear). Therefore, in order to promote bonding between a plurality of hydroxyl groups in a fluorinated ether compound and active sites on a protective layer, the present inventors have focused on the molecular structure of the fluorinated ether compound and conducted extensive investigations, which have led to the completion of the present invention.

[0026] The fluorine-containing ether compound, the lubricant for magnetic recording media (hereinafter sometimes abbreviated as "lubricant"), and the magnetic recording media of the present invention will be described in detail below. Note that the present invention is not limited to the following embodiments.

[0027] [Fluorine-containing ether compounds] The fluorine-containing ether compound of the present embodiment is represented by the following formula (1). R 1 -(O(CH2) a ) b -[A]-[B]-O-CH2-R 2-CH2-R 3 (1) (In formula (1), R 1 is either an alkyl group which may have a substituent, or an organic group having at least one double bond or triple bond. a is an integer of 2 to 4, and b is 0 or 1. [A] is represented by the following formula (2). In formula (2), c is 1 or 2. [B] is represented by the following formula (3). In formula (3), d is 0 or 1, and e is an integer of 2 to 4, provided that the sum of the values ​​of c in formula (2) and d in formula (3) is 2. R 2 is a perfluoropolyether chain. 3 is represented by the following formula (4), where f is an integer of 2 to 5.

[0028] [ka]

[0029] In the fluorine-containing ether compound represented by formula (1), R 1 is a terminal group, and is either an alkyl group which may have a substituent, or an organic group which has at least one double bond or triple bond. The alkyl group which may have a substituent, and the organic group which has at least one double bond or triple bond may contain any of an oxygen atom, a sulfur atom, and a nitrogen atom.

[0030] R 1 is an alkyl group having 1 to 6 carbon atoms, or an alkyl group having 1 to 6 carbon atoms and having a substituent. Examples of the substituent include a fluoro group or a cyano group, and one or more hydrogen atoms of the alkyl group may be substituted. All of the hydrogen atoms of the alkyl group may be substituted with a substituent. Moreover, the alkyl group having 1 to 6 carbon atoms and the alkyl group having 1 to 6 carbon atoms and having a substituent may be linear or branched.

[0031] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group and structural isomers thereof, and an n-hexyl group and structural isomers thereof.

[0032] Examples of the alkyl group having 1 to 6 carbon atoms in which one or more hydrogen atoms are substituted with a fluoro group include a trifluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, a perfluorohexyl group, a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,2,2,2,2-hexafluoroisopropyl group, a 2,2,3,3,4,4,4-heptafluorobutyl group, a 2,2,3,3,4,4,5,5,5-nonafluoropentyl group, and a 2,2,3,3,4,4,5,5,6,6,6-undecafluorohexyl group.

[0033] The number of cyano groups in the alkyl group having 1 to 6 carbon atoms in which one or more hydrogen atoms have been substituted with a cyano group may be 1 or 2 or more. If the number of cyano groups is large, the polarity of the fluorine-containing ether compound becomes too high, so the number of cyano groups is preferably 2 or less, and most preferably 1. Examples of the alkyl group having 1 to 6 carbon atoms in which one or more hydrogen atoms have been substituted with a cyano group include a 2-cyanoethyl group, a 3-cyanopropyl group, a 4-cyanobutyl group, a 5-cyanopentyl group, a 6-cyanohexyl group, a 2-cyano-1-methylethyl group, and a 2,2'-dicyanoisopropyl group.

[0034] The organic group having at least one double bond or triple bond is preferably any one of an organic group having 6 to 12 carbon atoms and containing an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms and containing an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms, and may be linear or branched.

[0035] Examples of the organic group having 6 to 12 carbon atoms and having an aromatic hydrocarbon include a phenyl group, a methoxyphenyl group, a dimethoxyphenyl group, a cyanophenyl group, a dicyanophenyl group, a fluorinated phenyl group, a naphthyl group, a methoxynaphthyl group, a benzyl group, a methoxybenzyl group, a phenethyl group, a methoxyphenethyl group, a fluorinated phenethyl group, a naphthylmethyl group, and a naphthylethyl group. However, when the aromatic hydrocarbon has a substituent, the substitution position may be anywhere.

[0036] Examples of the organic group having 3 to 10 carbon atoms and an aromatic heterocycle include a pyrrolyl group, a pyrazolyl group, a methylpyrazolylmethyl group, an imidazolyl group, a furyl group, a furfuryl group, an oxazolyl group, an isoxazolyl group, a thienyl group, a thienylmethyl group, a thienylethyl group, a thiazolyl group, a methylthiazolylethyl group, an isothiazolyl group, a pyridyl group, a pyrimidinyl group, a pyridazinyl group, a pyrazinyl group, an indolinyl group, a benzofuranyl group, a benzothienyl group, a benzimidazolyl group, a benzoxazolyl group, a benzothiazolyl group, a benzopyrazolyl group, a benzoisoxazolyl group, a benzoisothiazolyl group, a quinolyl group, an isoquinolyl group, a quinazolinyl group, a quinoxalinyl group, a phthalazinyl group, and a cinnolinyl group.

[0037] Examples of alkenyl groups having 2 to 8 carbon atoms include vinyl groups, allyl groups, 1-propenyl groups, isopropenyl groups, 3-butenyl groups and structural isomers thereof, 4-pentenyl groups and structural isomers thereof, 5-hexenyl groups and structural isomers thereof, 6-heptenyl groups and structural isomers thereof, and 7-octenyl groups and structural isomers thereof.

[0038] Examples of the alkynyl group having 3 to 8 carbon atoms include a 1-propynyl group, a propargyl group, a 3-butynyl group and its structural isomers, a 4-pentynyl group and its structural isomers, a 5-hexynyl group and its structural isomers, a 6-heptynyl group and its structural isomers, and a 7-octynyl group and its structural isomers.

[0039] R in the fluorine-containing ether compound represented by formula (1) 1From the viewpoint of availability and / or ease of synthesis, is preferably a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,2,2,2,2-hexafluoroisopropyl group, a 2-cyanoethyl group, a 3-cyanopropyl group, a 4-cyanobutyl group, a phenyl group, a methoxyphenyl group, a cyanophenyl group, a phenethyl group, a thienylethyl group, an N-methylpyrazolylmethyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, a propargyl group, a 3-butynyl group, or a 4-pentynyl group, and is most preferably a methyl group, an ethyl group, an n-propyl group, a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 3-cyanopropyl group, a 4-cyanobutyl group, a methoxyphenyl group, a cyanophenyl group, an allyl group, or a 3-butenyl group.

[0040] In the fluorinated ether compound of the present embodiment, a in formula (1) is an integer of 2 to 4. b in formula (1) is 0 or 1. When b is 0, the proportion of fluorine atoms in the fluorinated ether compound molecule decreases, and it is possible to prevent the surface free energy of the entire molecule from increasing. When b is 1, the terminal group R 1 and [A] represented by formula (2) are bonded via an ether bond, and the ether bond imparts flexibility to the fluorinated ether compound represented by formula (1), thereby obtaining the effect of making it easy to be adsorbed to the protective layer. When b is 1, a is preferably an integer of 2 to 3, and more preferably 2. When a is 2, the proportion of fluorine atoms in the fluorinated ether compound molecule decreases, and it is possible to suppress an increase in the surface free energy of the entire molecule. In addition, when a is 1, it is chemically unstable and tends to be easily decomposed, so a is set to an integer of 2 to 4.

[0041] In the fluorine-containing ether compound represented by formula (1), [A] is represented by formula (2), and [B] is a divalent linking group represented by formula (3). Formula (1) always has two secondary hydroxyl groups, combining [A] and [B], and the carbon atoms to which the hydroxyl groups are bonded are bonded via a linking group consisting of a methylene group (-CH2-) and an ether bond (-O-). Therefore, the distance between the hydroxyl groups of the two hydroxyl groups contained in the -[A]-[B]- structure is appropriate. Moreover, by having an etheric oxygen atom, the -[A]-[B]- structure imparts appropriate flexibility to the molecular structure of the fluorine-containing ether compound represented by formula (1). For these reasons, when a lubricating layer containing the fluorine-containing ether compound of this embodiment is formed on a protective layer, the two hydroxyl groups in the -[A]-[B]- structure are likely to participate in the bonding between the active sites on the protective layer and the lubricating layer. Therefore, the lubricating layer containing the fluorine-containing ether compound of this embodiment has excellent adhesion to the protective layer. As a result, pick-up and spin-off can be suppressed.

[0042] In formula (2), c is 1 or 2, and in formula (3), d is 0 or 1, and e is an integer of 2 to 4. However, the sum of the values ​​of c and d is always 2. From the viewpoint of adhesion to the protective layer, it is preferable that c=2, d=0 or c=1, d=1. When c=2, d=0, the directions in which the hydroxyl groups are three-dimensionally arranged are the same, and the hydroxyl groups tend to be easily adsorbed to the protective layer. When c=1, d=1, the distance between the hydroxyl groups contained in the -[A]-[B]- structure becomes longer, which reduces the interaction (e.g., hydrogen bond) in the fluorine-containing ether compound represented by formula (1), and the affinity with the protective layer can be increased. When c=1, d=1, the value of e is preferably an integer of 2 to 3, and most preferably 2.

[0043] The fluorine-containing ether compound of the present embodiment is represented by the formula (1), 2When a lubricant containing a fluorine-containing ether compound is applied onto a protective layer to form a lubricating layer, the PFPE chain coats the surface of the protective layer and imparts lubricity to the lubricating layer, thereby reducing the friction between the magnetic head and the protective layer. 2 is not particularly limited and can be appropriately selected depending on the performance required of the lubricant containing the fluorine-containing ether compound. Examples of the PFPE chain include perfluoromethylene oxide polymers, perfluoroethylene oxide polymers, perfluoro-n-propylene oxide polymers, perfluoroisopropylene oxide polymers, and copolymers thereof.

[0044] Specifically, R in formula (1) 2 is preferably any one of the following formulas (5) to (8). 2 When is any one of the formulas (5) to (8), the fluorine-containing ether compound provides a lubricating layer having good lubricity. The order of the repeating units (CF2-CF2-O) and (CF2-O) in formula (5) is not particularly limited. In formula (5), the number g of (CF2-CF2-O) and the number h of (CF2-O) showing the average degree of polymerization may be the same or different. Formula (5) may include any of random copolymers, block copolymers, and alternating copolymers consisting of monomer units (CF2-CF2-O) and (CF2-O). -CF2O-(CF2CF2O) g -(CF2O) h -CF2- (5) (In formula (5), g and h are average degrees of polymerization, g represents 3 to 8, and h represents 3 to 8.) -CF2O-(CF2CF2O) i -CF2- (6) (In formula (6), i is the average degree of polymerization and represents 5 to 13.) -CF2CF2O-(CF2CF2CF2O) j -CF2CF2- (7) (In formula (7), j is the average degree of polymerization and represents 3 to 8.) -CF(CF3)-(OCF(CF3)CF2) k -OCF(CF3)- (8) (In formula (8), k is the average degree of polymerization and represents 3 to 8.)

[0045] In formula (5), g indicating the average degree of polymerization is 3 to 8, preferably 4 to 7, and more preferably 4 to 5. h indicating the average degree of polymerization is 3 to 8, preferably 4 to 7, and more preferably 4 to 5.

[0046] In formula (6), when i is 5 to 13, the number average molecular weight of the fluorinated ether compound of the present embodiment tends to fall within the preferred range.

[0047] In formula (7), when j is 3 to 8, the number average molecular weight of the fluorinated ether compound of the present embodiment tends to fall within the preferred range.

[0048] In formula (8), when k is 3 to 8, the number average molecular weight of the fluorinated ether compound of the present embodiment tends to fall within the preferred range.

[0049] R in formula (1) 2 is any one of the formulas (5) to (8), the synthesis of the fluorine-containing ether compound is easy, which is preferable. 2 When is any one of formulas (5) to (8), the ratio of the number of oxygen atoms (the number of ether bonds (-O-)) to the number of carbon atoms in the PFPE chain and the arrangement of oxygen atoms in the PFPE chain are appropriate. Therefore, the fluorine-containing ether compound has an appropriate hardness. Therefore, the fluorine-containing ether compound applied on the protective layer is unlikely to aggregate on the protective layer, and a thinner lubricating layer can be formed with a sufficient coverage. In particular, R in formula (1)2 is formula (5), it is more preferable since the raw materials are easily available.

[0050] In the fluorine-containing ether compound of the present embodiment represented by the above formula (1), R 3 is a terminal group represented by formula (4). 3 has two secondary hydroxyl groups and one primary hydroxyl group, and the carbon atoms to which the hydroxyl groups are bonded are linked via a linking group consisting of a methylene group (-CH2-) and an ether bond (-O-). 3 The three hydroxyl groups contained in it have the appropriate distance between them. In addition, the presence of an ether oxygen atom makes R 3 imparts appropriate flexibility to the molecular structure of the fluorine-containing ether compound represented by formula (1). For these reasons, when a lubricating layer containing the fluorine-containing ether compound of this embodiment is formed on a protective layer, R 3 The three hydroxyl groups in the lubricating layer are likely to be involved in the binding between the active points on the protective layer and the lubricating layer. Therefore, the lubricating layer containing the fluorine-containing ether compound of this embodiment has excellent adhesion to the protective layer. As a result, the fluorine-containing ether compound that is not in contact (adsorbed) with the protective layer can be prevented from coagulating and adhering to the magnetic head as foreign matter (smear), thereby suppressing pick-up. In addition, the spin-off, which is a decrease in the thickness of the lubricating layer due to scattering and evaporation caused by centrifugal force and / or heat during high-speed rotation, can be suppressed.

[0051] In formula (4), f is an integer of 2 to 5. More preferably, f is an integer of 2 to 3, and most preferably 2. When f is 1, the structure is stabilized by the regular arrangement of five-membered ring-type intramolecular hydrogen bonds between the ether oxygen atoms and the hydroxyl groups in formula (4), resulting in a decrease in adhesion to the protective layer. By setting f to 2 or more and disrupting the regular arrangement and inhibiting the intramolecular interaction of the hydroxyl groups, adhesion to the protective layer is greatly improved. When f is 6 or more, the proportion of fluorine atoms in the fluorine-containing ether compound molecule decreases, undesirably increasing the surface free energy of the entire molecule.

[0052] In the fluorine-containing ether compound of the present embodiment represented by formula (1), two hydroxyl groups contained in the -[A]-[B]- structure and R 3 The three hydroxyl groups in 2 (PFPE chain) is arranged in a well-balanced manner. In addition, the hydroxyl groups at each end are appropriately spaced from each other and have a moderately flexible structure, so that they are easily involved in the bonding between the active site on the protective layer and the lubricating layer. Therefore, the fluorine-containing ether compound of this embodiment shows excellent adhesion properties due to a synergistic effect, since the hydroxyl groups at both ends of the PFPE chain can be effectively adsorbed to the protective layer. From the above, the lubricating layer containing the fluorinated ether compound of this embodiment has excellent adhesion to the protective layer, and as a result, pick-up and spin-off can be suppressed.

[0053] Specifically, the fluorinated ether compound represented by formula (1) is preferably any of the compounds represented by the following formulae (A1) to (T1). Note that the repeat numbers represented by ma1 to mt1 and na1 to nt1 in formulae (A1) to (T1) are values ​​indicating the average degree of polymerization, and are not necessarily integers.

[0054] [ka] (In formula (A1), ma1 and na1 represent average degrees of polymerization, ma1 being 3 to 8 and na1 being 3 to 8.) (In formula (A2), na2 represents the average degree of polymerization, and na2 is 5 to 13.) (In formula (A3), na3 represents the average degree of polymerization, and na3 is 3 to 8.)

[0055] [ka] (In formula (B1), mb1 and nb1 represent average degrees of polymerization, mb1 being 3 to 8, and nb1 being 3 to 8.) (In formula (B2), nb2 represents the average degree of polymerization, and nb2 is 5 to 13.) (In formula (B3), nb3 represents the average degree of polymerization, and nb3 is 3 to 8.)

[0056] [ka] (In formula (C1), mc1 and nc1 represent average degrees of polymerization, mc1 being 3 to 8 and nc1 being 3 to 8.) (In formula (D1), md1 and nd1 represent average degrees of polymerization, where md1 is 3 to 8 and nd1 is 3 to 8.) (In formula (E1), me1 and ne1 represent average degrees of polymerization, me1 being 3 to 8 and ne1 being 3 to 8.) (In formula (F1), mf1 and nf1 represent average degrees of polymerization, mf1 being 3 to 8 and nf1 being 3 to 8.)

[0057] [ka] (In formula (G1), mg1 and ng1 represent average degrees of polymerization, mg1 being 3 to 8, and ng1 being 3 to 8.) (In formula (H1), mh1 and nh1 represent average degrees of polymerization, mh1 being 3 to 8, and nh1 being 3 to 8.)

[0058] [ka] (In formula (I1), mi1 and ni1 represent average degrees of polymerization, mi1 being 3 to 8 and ni1 being 3 to 8.) (In formula (J1), mj1 and nj1 represent average degrees of polymerization, mj1 being 3 to 8 and nj1 being 3 to 8.) (In formula (K1), mk1 and nk1 represent average degrees of polymerization, mk1 being 3 to 8 and nk1 being 3 to 8.) (In formula (L1), ml1 and nl1 represent the average degree of polymerization, ml1 being 3 to 8, and nl1 being 3 to 8.)

[0059] [ka] (In formula (M1), mm1 and nm1 represent average degrees of polymerization, mm1 being 3 to 8, and nm1 being 3 to 8.) (In formula (N1), mn1 and nn1 represent average degrees of polymerization, mn1 being 3 to 8, and nn1 being 3 to 8.)

[0060] [ka] (In formula (O1), mo1 and no1 represent average degrees of polymerization, mo1 being 3 to 8 and no1 being 3 to 8.) (In formula (P1), mp1 and np1 represent average degrees of polymerization, mp1 being 3 to 8, and np1 being 3 to 8.)

[0061] [ka] (In formula (Q1), mq1 and nq1 represent average degrees of polymerization, mq1 being 3 to 8 and nq1 being 3 to 8.) (In formula (R1), mr1 and nr1 represent average degrees of polymerization, mr1 being 3 to 8 and nr1 being 3 to 8.)

[0062] [ka] (In formula (S1), ms1 and ns1 represent average degrees of polymerization, where ms1 is 3 to 8 and ns1 is 3 to 8.) (In formula (T1), mt1 and nt1 represent average degrees of polymerization, mt1 being 3 to 8 and nt1 being 3 to 8.)

[0063] The fluorinated ether compound of the present embodiment has a number average molecular weight (Mn) preferably in the range of 1000 to 2300, more preferably in the range of 1100 to 2100, particularly preferably in the range of 1200 to 1800, and most preferably in the range of 1200 to 1600. When the number average molecular weight is 1000 or more, the lubricant containing the fluorine-containing ether compound of this embodiment is difficult to evaporate.Therefore, when the number average molecular weight is 1000 or more, pick-up and spin-off can be prevented.In addition, when the number average molecular weight is 2300 or less, the viscosity of the fluorine-containing ether compound is not too high, and the viscosity is suitable for a lubricant.In addition, when the number average molecular weight exceeds 2300, the viscosity of the fluorine-containing ether compound is high, and handling tends to be poor. From the viewpoint of the ease of obtaining raw materials for the PFPE chain, the number average molecular weight is preferably within the range of 1100 to 2100. When the number average molecular weight is within the range of 1200 to 1800, the coating rate does not deteriorate even if the film thickness of the lubricating layer is thinned, and chemical resistance and wear resistance can be maintained. When the number average molecular weight is within the range of 1200 to 1600, the best balance of performance is obtained from the viewpoints of preventing pick-up and spin-off and thinning the lubricating layer.

[0064] "Manufacturing method" The method for producing the fluorinated ether compound of the present embodiment is not particularly limited, and the compound can be produced by a conventionally known production method. The fluorinated ether compound of the present embodiment can be produced, for example, by the production method shown below. First, R in Equation (1) 2 A fluorine-based compound having a PFPE chain corresponding to the above and a hydroxymethyl group (-CHOH) at each end of the molecule is prepared. Next, the hydroxyl group of the hydroxymethyl group located at one end of the fluorine-based compound is converted to R 1 -(O(CH2) a ) b The hydroxyl group of the hydroxymethyl group located at the other end is then replaced with a group consisting of -[A]-[B]-O- (first reaction). 3 (second reaction) The first and second reactions can be carried out using a conventionally known method and can be appropriately determined depending on the type of the terminal in formula (1), etc. In addition, either the first or second reaction can be carried out first.

[0065] [Lubricants for magnetic recording media] The lubricant for a magnetic recording medium of this embodiment contains a fluorine-containing ether compound represented by formula (1). The lubricant of the present embodiment can be used by mixing, as necessary, known materials used as lubricant materials, so long as the properties resulting from the inclusion of the fluorinated ether compound represented by formula (1) are not impaired. Specific examples of known materials include FOMBLIN (registered trademark) ZDIAC, FOMBLIN ZDEAL, FOMBLIN AM-2001 (all manufactured by Solvay Solexis), Moresco A20H (manufactured by Moresco), etc. The known material to be mixed with the lubricant of the present embodiment preferably has a number average molecular weight of 1,000 to 10,000.

[0066] When the lubricant of the present embodiment contains a material other than the fluorinated ether compound represented by formula (1), the content of the fluorinated ether compound represented by formula (1) in the lubricant of the present embodiment is preferably 50% by mass or more, more preferably 70% by mass or more. The content of the fluorinated ether compound represented by formula (1) may be 80% by mass or more, or may be 90% by mass or more. Since the lubricant of this embodiment contains a fluorinated ether compound represented by formula (1), it is possible to obtain a lubricating layer that has good adhesion to the protective layer and can suppress pick-up and spin-off even when the molecular weight is reduced.

[0067] [Magnetic recording media] The magnetic recording medium of this embodiment has at least a magnetic layer, a protective layer, and a lubricating layer provided in this order on a substrate. In the magnetic recording medium of this embodiment, one or more underlayers may be provided between the substrate and the magnetic layer, if necessary. Also, an adhesive layer and / or a soft magnetic layer may be provided between the underlayer and the substrate. FIG. 1 is a schematic cross-sectional view showing one embodiment of the magnetic recording medium of the present invention. The magnetic recording medium 10 of this embodiment has a structure in which an adhesive layer 12, a soft magnetic layer 13, a first underlayer 14, a second underlayer 15, a magnetic layer 16, a protective layer 17, and a lubricating layer 18 are sequentially provided on a substrate 11.

[0068] "substrate" The substrate 11 may be, for example, a non-magnetic substrate in which a film made of NiP or a NiP alloy is formed on a base made of a metal or alloy material such as Al or an Al alloy. Furthermore, the substrate 11 may be a non-magnetic substrate made of a non-metallic material such as glass, ceramics, silicon, silicon carbide, carbon, or resin, or a non-magnetic substrate having a NiP or NiP alloy film formed on a base made of these non-metallic materials. Glass substrates are suitable for achieving high recording density because they have rigidity and excellent smoothness. Examples of glass substrates include aluminosilicate glass substrates, and chemically strengthened aluminosilicate glass substrates are particularly suitable. The main surface of the substrate 11 is preferably ultra-smooth with a roughness of Rmax of 6 nm or less and Ra of 0.6 nm or less. Note that the surface roughnesses Rmax and Ra referred to here are based on the JIS B0601 standard.

[0069] "Adhesion layer" The adhesive layer 12 prevents the progress of corrosion of the substrate 11, which occurs when the substrate 11 and the soft magnetic layer 13 provided on the adhesive layer 12 are disposed in contact with each other. The material of the adhesive layer 12 can be appropriately selected from, for example, Cr, a Cr alloy, Ti, a Ti alloy, CrTi, NiAl, an AlRu alloy, etc. The adhesive layer 12 can be formed by, for example, a sputtering method.

[0070] "Soft magnetic layer" The soft magnetic layer 13 preferably has a structure in which a first soft magnetic film, an intermediate layer made of a Ru film, and a second soft magnetic film are laminated in this order. That is, the soft magnetic layer 13 preferably has a structure in which the intermediate layer made of a Ru film is sandwiched between two soft magnetic films, and the soft magnetic films above and below the intermediate layer are anti-ferro-coupling (AFC). The first and second soft magnetic films may be made of a material such as a CoZrTa alloy or a CoFe alloy. It is preferable to add any one of Zr, Ta, and Nb to the CoFe alloy used for the first and second soft magnetic films. This promotes the amorphization of the first and second soft magnetic films, and improves the orientation of the first underlayer (seed layer). At the same time, it becomes possible to reduce the flying height of the magnetic head. The soft magnetic layer 13 can be formed by, for example, a sputtering method.

[0071] "First base layer" The first underlayer 14 is a layer for controlling the orientation and crystal size of the second underlayer 15 and magnetic layer 16 provided thereon. Examples of the first underlayer 14 include a Cr layer, a Ta layer, a Ru layer, or a CrMo alloy layer, a CoW alloy layer, a CrW alloy layer, a CrV alloy layer, and a CrTi alloy layer. The first underlayer 14 can be formed by, for example, a sputtering method.

[0072] "Second base layer" The second underlayer 15 is a layer that controls good orientation of the magnetic layer 16. The second underlayer 15 is preferably a layer made of Ru or a Ru alloy. The second underlayer 15 may be a layer consisting of one layer, or may be composed of multiple layers. When the second underlayer 15 is composed of multiple layers, all the layers may be composed of the same material, or at least one layer may be composed of a different material. The second underlayer 15 can be formed by, for example, a sputtering method.

[0073] "Magnetic layer" The magnetic layer 16 is a magnetic film with an easy axis of magnetization oriented perpendicular or parallel to the substrate surface. The magnetic layer 16 is a layer containing Co and Pt, and may further contain an oxide, Cr, B, Cu, Ta, Zr, etc., in order to improve the SNR (Signal to Noise Ratio) characteristics. The oxides contained in the magnetic layer 16 include SiO2, SiO, Cr2O3, CoO, Ta2O3, TiO2, and the like. The magnetic layer 16 may be composed of a single layer, or may be composed of multiple magnetic layers made of materials with different compositions.

[0074] For example, when the magnetic layer 16 is composed of three layers, a first magnetic layer, a second magnetic layer, and a third magnetic layer, stacked in order from the bottom, the first magnetic layer preferably has a granular structure made of a material containing Co, Cr, and Pt and further containing an oxide. As the oxide contained in the first magnetic layer, for example, oxides such as Cr, Si, Ta, Al, Ti, Mg, and Co are preferably used. Among them, TiO2, Cr2O3, SiO2, and the like can be particularly preferably used. In addition, the first magnetic layer is preferably made of a composite oxide to which two or more kinds of oxides are added. Among them, Cr2O3-SiO2, Cr2O3-TiO2, SiO2-TiO2, and the like can be particularly preferably used. The first magnetic layer may contain one or more elements selected from B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, and Re, in addition to Co, Cr, Pt, and oxides. The second magnetic layer may be made of the same material as the first magnetic layer. The second magnetic layer preferably has a granular structure. The third magnetic layer preferably has a non-granular structure made of a material that contains Co, Cr, and Pt and does not contain oxides. In addition to Co, Cr, and Pt, the third magnetic layer may contain one or more elements selected from B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, Re, and Mn.

[0075] When the magnetic layer 16 is formed of multiple magnetic layers, it is preferable to provide a nonmagnetic layer between adjacent magnetic layers. When the magnetic layer 16 is formed of three layers, a first magnetic layer, a second magnetic layer, and a third magnetic layer, it is preferable to provide a nonmagnetic layer between the first magnetic layer and the second magnetic layer and between the second magnetic layer and the third magnetic layer. The non-magnetic layer provided between adjacent magnetic layers in the magnetic layer 16 can suitably be made of, for example, Ru, a Ru alloy, a CoCr alloy, or a CoCrX1 alloy (X1 represents one or more elements selected from Pt, Ta, Zr, Re, Ru, Cu, Nb, Ni, Mn, Ge, Si, O, N, W, Mo, Ti, V, and B).

[0076] For the non-magnetic layer provided between adjacent magnetic layers of the magnetic layer 16, it is preferable to use an alloy material containing an oxide, a metal nitride, or a metal carbide. Specifically, for example, SiO2, Al2O3, Ta2O5, Cr2O3, MgO, Y2O3, TiO2, etc. can be used as the oxide. For example, AlN, Si3N4, TaN, CrN, etc. can be used as the metal nitride. For example, TaC, BC, SiC, etc. can be used as the metal carbide. The nonmagnetic layer can be formed by, for example, a sputtering method.

[0077] In order to achieve higher recording density, the magnetic layer 16 is preferably a magnetic layer for perpendicular magnetic recording in which the axis of easy magnetization is oriented perpendicular to the substrate surface, but may also be a magnetic layer for in-plane magnetic recording. The magnetic layer 16 may be formed by any known method such as vapor deposition, ion beam sputtering, magnetron sputtering, etc. The magnetic layer 16 is usually formed by sputtering.

[0078] "Protective layer" The protective layer 17 protects the magnetic layer 16. The protective layer 17 may be made of a single layer or multiple layers. Examples of materials for the protective layer 17 include carbon, carbon containing nitrogen, and silicon carbide. A carbon-based protective layer can be preferably used as the protective layer 17, and an amorphous carbon protective layer is particularly preferred. When the protective layer 17 is a carbon-based protective layer, the interaction with the polar group (particularly a hydroxyl group) contained in the fluorine-containing ether compound in the lubricating layer 18 is further enhanced, which is preferable. The adhesion between the carbon-based protective layer and the lubricating layer 18 can be controlled by making the carbon-based protective layer hydrogenated carbon and / or nitrogenated carbon and adjusting the hydrogen content and / or nitrogen content in the carbon-based protective layer.

[0079] The hydrogen content in the carbon-based protective layer is preferably 3 to 20 atomic % when measured by hydrogen forward scattering (HFS), and the nitrogen content in the carbon-based protective layer is preferably 4 to 12 atomic % when measured by X-ray photoelectron spectroscopy (XPS). The hydrogen and / or nitrogen contained in the carbon-based protective layer does not need to be uniformly contained throughout the carbon-based protective layer. For example, the carbon-based protective layer is preferably a composition gradient layer in which the lubricating layer 18 side of the protective layer 17 contains nitrogen, and the magnetic layer 16 side of the protective layer 17 contains hydrogen. In this case, the adhesion between the magnetic layer 16 and the lubricating layer 18 and the carbon-based protective layer is further improved. This is because the nitrogen in the protective layer 17 acts as an active site and promotes bonding with the lubricating layer. The hydrogen or nitrogen in the carbon-based protective layer acts as an active site.

[0080] The thickness of the protective layer 17 is preferably 1 nm to 7 nm. If the thickness of the protective layer 17 is 1 nm or more, sufficient performance as the protective layer 17 can be obtained. If the thickness of the protective layer 17 is 7 nm or less, it is preferable from the viewpoint of making the protective layer 17 thinner.

[0081] The protective layer 17 can be formed by sputtering using a target material containing carbon, chemical vapor deposition (CVD) using a hydrocarbon raw material such as ethylene or toluene, or ion beam deposition (IBD). When a carbon-based protective layer is formed as the protective layer 17, it can be deposited by, for example, a DC magnetron sputtering method. In particular, when a carbon-based protective layer is formed as the protective layer 17, it is preferable to deposit an amorphous carbon protective layer by a plasma CVD method. The amorphous carbon protective layer deposited by the plasma CVD method has a uniform surface with small roughness.

[0082] "Lubricant layer" The lubricating layer 18 prevents contamination of the magnetic recording medium 10. In addition, the lubricating layer 18 reduces the frictional force of the magnetic head of the magnetic recording and reproducing device that slides on the magnetic recording medium 10, thereby improving the durability of the magnetic recording medium 10. 1, the lubricating layer 18 is formed on and in contact with the protective layer 17. The lubricating layer 18 contains the fluorine-containing ether compound of this embodiment. When the protective layer 17 disposed below the lubricating layer 18 is a carbon-based protective layer, the lubricating layer 18 is bonded with a high bonding strength to the protective layer 17. As a result, even if the thickness of the lubricating layer 18 is thin, it is easy to obtain a magnetic recording medium 10 in which the surface of the protective layer 17 is covered with a high coverage rate, and contamination of the surface of the magnetic recording medium 10 can be effectively prevented.

[0083] The average thickness of the lubricating layer 18 is preferably 0.5 nm (5 Å) to 3.0 nm (30 Å), and more preferably 0.5 nm (5 Å) to 2.0 nm (20 Å). When the average thickness of the lubricating layer 18 is 0.5 nm or more, the lubricating layer 18 is formed with a uniform thickness without being island-shaped or mesh-shaped. Therefore, the surface of the protective layer 17 can be covered with the lubricating layer 18 with a high coverage. In addition, by setting the average thickness of the lubricating layer 18 to 3.0 nm or less, the lubricating layer 18 can be made sufficiently thin, and the flying height of the magnetic head can be sufficiently reduced.

[0084] If the surface of the protective layer 17 is not covered with the lubricating layer 18 at a sufficiently high coverage rate, environmental substances adsorbed to the surface of the magnetic recording medium 10 will pass through the gaps in the lubricating layer 18 and penetrate underneath the lubricating layer 18. The environmental substances that penetrate underneath the lubricating layer 18 will be adsorbed and bonded to the protective layer 17 to generate contaminants. Then, during magnetic recording and reproduction, these contaminants (aggregated components) will adhere (transfer) to the magnetic head as smear, damaging the magnetic head or degrading the magnetic recording and reproduction characteristics of the magnetic recording and reproduction device.

[0085] Examples of environmental substances that generate pollutants include siloxane compounds (cyclic siloxanes, linear siloxanes), ionic impurities, hydrocarbons with relatively high molecular weights such as octacosane, and plasticizers such as dioctyl phthalate. Examples of metal ions contained in ionic impurities include sodium ions and potassium ions. Examples of inorganic ions contained in ionic impurities include chloride ions, bromide ions, nitrate ions, sulfate ions, and ammonium ions. Examples of organic ions contained in ionic impurities include oxalate ions and formate ions.

[0086] "Method of forming lubricating layer" One method for forming the lubricating layer 18 is to prepare a magnetic recording medium in the middle of manufacture in which all layers up to the protective layer 17 are formed on the substrate 11, and then apply a solution for forming a lubricating layer onto the protective layer 17 and dry it. The lubricant layer forming solution can be obtained by dispersing and dissolving the lubricant for magnetic recording media of the above-mentioned embodiment in a solvent as necessary, and adjusting the viscosity and concentration to be suitable for the coating method. Examples of the solvent used in the lubricant layer forming solution include fluorine-based solvents such as Vertrel (registered trademark) XF (product name, manufactured by Mitsui DuPont Fluorochemicals).

[0087] The method for applying the solution for forming the lubricating layer is not particularly limited, but examples thereof include spin coating, spraying, paper coating, and dipping. When using the dipping method, for example, the following method can be used. First, the substrate 11 on which each layer up to the protective layer 17 has been formed is immersed in the lubricant layer forming solution placed in the immersion tank of a dip coater. Next, the substrate 11 is lifted from the immersion tank at a predetermined speed. In this way, the lubricant layer forming solution is applied to the surface of the substrate 11 above the protective layer 17. By using the dipping method, the lubricant layer forming solution can be applied uniformly onto the surface of the protective layer 17, and the lubricant layer 18 can be formed on the protective layer 17 with a uniform thickness.

[0088] In this embodiment, it is preferable to perform a heat treatment on the substrate 11 on which the lubricating layer 18 is formed. By performing the heat treatment, the adhesion between the lubricating layer 18 and the protective layer 17 is improved, and the adhesive force between the lubricating layer 18 and the protective layer 17 is improved. The heat treatment temperature is preferably 100 to 180° C. If the heat treatment temperature is 100° C. or higher, the effect of improving the adhesion between the lubricating layer 18 and the protective layer 17 can be sufficiently obtained. Furthermore, by setting the heat treatment temperature to 180° C. or lower, thermal decomposition of the lubricating layer 18 can be prevented. The heat treatment time is preferably 10 to 120 minutes. In this embodiment, in order to further improve the adhesion of the lubricating layer 18 to the protective layer 17, the lubricating layer 18 of the substrate 11 may be irradiated with ultraviolet (UV) rays before or after the heat treatment.

[0089] The magnetic recording medium 10 of this embodiment has at least a magnetic layer 16, a protective layer 17, and a lubricating layer 18 provided in this order on a substrate 11. In the magnetic recording medium 10 of this embodiment, the lubricating layer 18 containing the above-mentioned fluorine-containing ether compound is formed on and in contact with the protective layer 17.

[0090] With conventional lubricants, it is difficult to reduce the thickness of the lubricating layer while maintaining the reliability and durability of the magnetic recording medium, and even when attempts are made to reduce the molecular weight of the fluorine-containing ether compound used in the lubricant to reduce the thickness, there is a problem of spin-off. Since the lubricant of this embodiment contains the fluorine-containing ether compound represented by formula (1), it is possible to form a lubricating layer that can suppress pick-up and spin-off even when the molecular weight is reduced.

[0091] Therefore, the lubricating layer 18 of this embodiment has good adhesion to the protective layer, and can suppress pick-up and spin-off even when the molecular weight is reduced. Therefore, the magnetic recording medium 10 of this embodiment has excellent reliability and durability. In addition, the lubricating layer 18 of this embodiment can further reduce the magnetic spacing, which can contribute to improving the recording density of the magnetic recording medium. Therefore, the magnetic recording medium 10 of this embodiment is particularly suitable as a magnetic disk to be mounted on a magnetic disk device of the LUL method (Load Unload method). EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0093] [NMR measurement method] The structures of the compounds obtained in the following Examples 1 to 54 were identified using AVANCEIII-400 manufactured by Bruker Biospin. 1 H-NMR and 19 This was done by F-NMR measurement. Approximately 10 mg of a sample to be used for NMR measurement was weighed out and dissolved in approximately 0.5 mL of deuterated acetone (with hexafluorobenzene added as a reference substance) and used for the measurement. 1 The reference for H-NMR chemical shifts was the acetone peak at 2.05 ppm. 19 The F-NMR chemical shift reference was set to −164.7 ppm relative to the hexafluorobenzene peak. The number average molecular weight of each compound shown in Tables 2 to 4 is 19 The calculation was based on the results of F-NMR measurement. 19 The number of repeating units of the PFPE chain was calculated from the integrated intensity of fluorine atoms measured by F-NMR to obtain the number average molecular weight.

[0094] [Example 1] Compound (A1) represented by the above formula (A1) (in formula (A1), ma1 indicating the average degree of polymerization is 3.4, and na1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, a compound represented by the following formula (10) was synthesized by the method shown below. Two equivalents of 3-buten-1-ol and one equivalent of epichlorohydrin were reacted to synthesize a compound (9) represented by the following formula (9). The obtained compound (9) was reacted with 3,4-dihydro-2H-pyran to protect the hydroxyl group with a tetrahydropyranyl group, and then the double bond on one side was oxidized using m-chloroperbenzoic acid to synthesize a compound (10) represented by the following formula (10).

[0095] [ka]

[0096] In addition, a compound represented by the following formula (12) was synthesized by the method shown below. The primary hydroxyl group of 3-allyloxy-1,2-propanediol was protected with a t-butyldimethylsilyl group. Thereafter, the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound to synthesize a compound (11) represented by the following formula (11). The obtained compound (11) was reacted with 2-(3-chloropropoxy)tetrahydropyran, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize a compound (12) represented by the following formula (12).

[0097] [ka]

[0098] In a 200 mL eggplant flask, add HOCH2CF2O (CF2CF2O) g (CF2O) hFluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), compound (10) (9.01 g) represented by the above formula (10), and t-BuOH (tertiary butyl alcohol) (40.0 mL) were charged and stirred at room temperature until homogenized. Furthermore, t-BuOK (potassium tertiary butoxide) (1.68 g) was added to the above-mentioned eggplant flask, heated to 70 ° C, and reacted by stirring for 12 hours. The reaction product was then cooled to 25°C, water was added, and further, Bertrel (registered trademark) XF (hereinafter sometimes referred to as "Bertrel XF") manufactured by Mitsui DuPont Fluorochemicals was added as a solvent to extract the organic layer, which was then washed with water. Anhydrous sodium sulfate was added to the organic layer to dehydrate it, and the desiccant was filtered off, and the filtrate was concentrated. The residue was purified by silica gel column chromatography to obtain compound (13) (22.0 g) represented by the following formula (13).

[0099] [ka] (In formula (13), m, which indicates the average degree of polymerization, is 3.4, and n, which indicates the average degree of polymerization, is 3.4.)

[0100] In a nitrogen gas atmosphere, compound (13) (22.0 g) represented by formula (13), compound (12) (7.36 g) represented by formula (12), and t-BuOH (tertiary butyl alcohol) (65.0 mL) were charged into a 200 mL recovery flask and stirred at room temperature until homogenized. Furthermore, t-BuOK (potassium tertiary butoxide) (0.67 g) was added to the recovery flask, heated to 70° C., and reacted with stirring for 16 hours. Thereafter, the obtained reaction product was cooled to 25° C., and a 7% hydrogen chloride / methanol reagent (104.2 g) was added thereto, followed by stirring at room temperature for 3 hours to carry out a deprotection reaction. The reaction product was neutralized by adding 7% sodium bicarbonate water (250 mL), and then the organic layer was extracted with Vertrel XF and washed with water. Anhydrous sodium sulfate was added to the organic layer to dehydrate it, and the drying agent was filtered off, and the filtrate was concentrated. The residue was purified by silica gel column chromatography to obtain 17.1 g of compound (A1).

[0101] The obtained compound (A1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.58-1.82(4H), 2.34(2H), 3.48-4.20(35H), 4.98(1H), 5.05(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0102] [Example 2] Compound (A1) represented by the above formula (A1) (in formula (A1), ma1 indicating the average degree of polymerization is 6.2, and na1 indicating the average degree of polymerization is 6.2) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 1 was carried out, except that fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 6.2, and h, which indicates the average degree of polymerization, is 6.2) was used, and 14.8 g of compound (A1) was obtained.

[0103] The obtained compound (A1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.58-1.82(4H), 2.34(2H), 3.48-4.20(35H), 4.98(1H), 5.05(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(12.4F), -78.48(2F), -80.66(2F), -89.16~-91.14(24.8F)

[0104] [Example 3] Compound (A1) represented by the above formula (A1) (in formula (A1), ma1 indicating the average degree of polymerization is 7.8, and na1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 1 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 14.2 g of compound (A1) was obtained.

[0105] The obtained compound (A1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1H-NMR (acetone-d6): δ[ppm]=1.58-1.82(4H), 2.34(2H), 3.48-4.20(35H), 4.98(1H), 5.05(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0106] [Example 4] A compound (A2) represented by the above formula (A2) (in formula (A2), na2 indicating the average degree of polymerization is 5.4) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) i The same procedure as in Example 1 was carried out except that fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i, indicating the average degree of polymerization, is 5.4) was used, and 13.4 g of compound (A2) was obtained.

[0107] The obtained compound (A2) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.59-1.81(4H), 2.34(2H), 3.40-4.20(35H), 4.99(1H), 5.08(1H), 5.84(1H) 19 F-NMR (acetone-d6): δ[ppm]=-78.57(4F), -88.92~-89.57(21.6F)

[0108] [Example 5] A compound (A2) represented by the above formula (A2) (in formula (A2), na2 indicating the average degree of polymerization is 9.7) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) i The same procedure as in Example 1 was carried out except that fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i, indicating the average degree of polymerization, is 9.7) was used, and 12.4 g of compound (A2) was obtained.

[0109] The obtained compound (A2) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.59-1.81(4H), 2.34(2H), 3.40-4.20(35H), 4.99(1H), 5.08(1H), 5.84(1H) 19 F-NMR (acetone-d6): δ[ppm]=-78.57(4F), -88.92~-89.57(38.8F)

[0110] [Example 6] A compound (A2) represented by the above formula (A2) (in formula (A2), na2 indicating the average degree of polymerization is 12.3) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) iThe same procedure as in Example 1 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i, indicating the average degree of polymerization, is 12.3) was used, and 11.1 g of compound (A2) was obtained.

[0111] The obtained compound (A2) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.59-1.81(4H), 2.34(2H), 3.40-4.20(35H), 4.99(1H), 5.08(1H), 5.84(1H) 19 F-NMR (acetone-d6): δ[ppm]=-78.57(4F), -88.92~-89.57(49.2F)

[0112] [Example 7] A compound (A3) represented by the above formula (A3) (in formula (A3), na3 indicating the average degree of polymerization is 3.1) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4), instead of fluoropolyether (number average molecular weight: 800, molecular weight distribution: 1.1), HOCH2CF2CF2O (CF2CF2CF2O) j The same procedure as in Example 1 was carried out, except that fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j, indicating the average degree of polymerization, is 3.1) was used, and 13.6 g of compound (A3) was obtained.

[0113] The obtained compound (A3) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1H-NMR (acetone-d6): δ[ppm]=1.58-1.82(4H), 2.34(2H), 3.38-4.25(35H), 4.98(1H), 5.08(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-84.22(12.4F), -86.40(4F), -124.30(4F), -130.08(6.2F)

[0114] [Example 8] A compound (A3) represented by the above formula (A3) (in formula (A3), na3 indicating the average degree of polymerization is 6.2) was obtained by the method described below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4), instead of fluoropolyether (number average molecular weight: 800, molecular weight distribution: 1.1), HOCH2CF2CF2O (CF2CF2CF2O) j The same procedure as in Example 1 was carried out, except that fluoropolyether (number average molecular weight 1,300, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j, indicating the average degree of polymerization, is 6.2) was used, and 14.1 g of compound (A3) was obtained.

[0115] The obtained compound (A3) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.58-1.82(4H), 2.34(2H), 3.38-4.25(35H), 4.98(1H), 5.08(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-84.22(24.8F), -86.40(4F), -124.30(4F), -130.08(12.4F)

[0116] [Example 9] A compound (A3) represented by the above formula (A3) (in formula (A3), na3 indicating the average degree of polymerization is 8) was obtained by the method shown below. In Example 1, HOCH2CF2O(CF2CF2O) g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4), instead of fluoropolyether (number average molecular weight: 800, molecular weight distribution: 1.1), HOCH2CF2CF2O (CF2CF2CF2O) j The same procedure as in Example 1 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j, indicating the average degree of polymerization, is 8) was used, and 11.1 g of compound (A3) was obtained.

[0117] The obtained compound (A3) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.58-1.82(4H), 2.34(2H), 3.38-4.25(35H), 4.98(1H), 5.08(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-84.22(32F), -86.40(4F), -124.30(4F), -130.08(16F)

[0118] [Example 10] Compound (B1) represented by the above formula (B1) (in formula (B1), mb1 indicating the average degree of polymerization is 3.4, and nb1 indicating the average degree of polymerization is 3.4) was obtained by the method shown below. First, compound (15) represented by the following formula (15) was synthesized by the method shown below. 1,3-diallyloxy-2-propanol was reacted with 3,4-dihydro-2H-pyran to synthesize a compound represented by the following formula (14). One double bond of the obtained compound (14) was oxidized using m-chloroperbenzoic acid to synthesize compound (15) represented by the following formula (15).

[0119] [ka]

[0120] The same operation as in Example 1 was performed, except that compound (15) (8.17 g) represented by formula (15) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 16.7 g of compound (B1).

[0121] The obtained compound (B1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0122] [Example 11] Compound (B1) represented by the above formula (B1) (in formula (B1), mb1 indicating the average degree of polymerization is 6.2, and nb1 indicating the average degree of polymerization is 6.2) was obtained by the method shown below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) hInstead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 6.2, and h, which indicates the average degree of polymerization, is 6.2) was used, and 16.2 g of compound (B1) was obtained.

[0123] The obtained compound (B1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(12.4F), -78.48(2F), -80.66(2F), -89.16~-91.14(24.8F)

[0124] [Example 12] Compound (B1) represented by the above formula (B1) (in formula (B1), mb1 indicating the average degree of polymerization is 7.8, and nb1 indicating the average degree of polymerization is 7.8) was obtained by the method shown below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) hThe same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.8 g of compound (B1).

[0125] The obtained compound (B1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0126] [Example 13] A compound (B2) represented by the above formula (B2) (in formula (B2), nb2 indicating the average degree of polymerization is 5.4) was obtained by the method shown below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) i The same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i, indicating the average degree of polymerization, is 5.4) was used, and 16.2 g of compound (B2) was obtained.

[0127] The obtained compound (B2) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.42-4.24(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-78.57(4F), -88.92~-89.57(21.6F)

[0128] [Example 14] A compound (B2) represented by the above formula (B2) (in formula (B2), nb2 indicating the average degree of polymerization is 9.7) was obtained by the method described below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) i The same procedure as in Example 10 was carried out except that fluoropolyether (number average molecular weight 1300, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i, indicating the average degree of polymerization, is 9.7) was used, and 16.1 g of compound (B2) was obtained.

[0129] The obtained compound (B2) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.42-4.24(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-78.57(4F), -88.92~-89.57(38.8F)

[0130] [Example 15] A compound (B2) represented by the above formula (B2) (in formula (B2), nb2 indicating the average degree of polymerization is 12.3) was obtained by the method described below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) i The same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein i, indicating the average degree of polymerization, is 12.3) was used, and 16.7 g of compound (B2) was obtained.

[0131] The obtained compound (B2) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.42-4.24(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-78.57(4F), -88.92~-89.57(49.2F)

[0132] [Example 16] A compound (B3) represented by the above formula (B3) (in formula (B3), nb3 indicating the average degree of polymerization is 3.1) was obtained by the method shown below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4), instead of fluoropolyether (number average molecular weight: 800, molecular weight distribution: 1.1), HOCH2CF2CF2O (CF2CF2CF2O) jThe same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j, indicating the average degree of polymerization, is 3.1) was used, and 14.6 g of compound (B3) was obtained.

[0133] The obtained compound (B3) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.38-4.19(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-84.22(12.4F), -86.40(4F), -124.30(4F), -130.08(6.2F)

[0134] [Example 17] A compound (B3) represented by the above formula (B3) (in formula (B3), nb3 indicating the average degree of polymerization is 6.2) was obtained by the method shown below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4), instead of fluoropolyether (number average molecular weight: 800, molecular weight distribution: 1.1), HOCH2CF2CF2O (CF2CF2CF2O) j The same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 1,300, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j, indicating the average degree of polymerization, is 6.2) was used, and 15.2 g of compound (B3) was obtained.

[0135] The obtained compound (B3) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.38-4.19(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-84.22(24.8F), -86.40(4F), -124.30(4F), -130.08(12.4F)

[0136] [Example 18] A compound (B3) represented by the above formula (B3) (in formula (B3), nb3 indicating the average degree of polymerization is 8) was obtained by the method shown below. In Example 10, HOCH2CF2O(CF2CF2O) g (CF2O) h CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 3.4, and h, which indicates the average degree of polymerization, is 3.4), instead of fluoropolyether (number average molecular weight: 800, molecular weight distribution: 1.1), HOCH2CF2CF2O (CF2CF2CF2O) j The same procedure as in Example 10 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CF2CH2OH (wherein j, indicating the average degree of polymerization, is 8) was used, and 12.5 g of compound (B3) was obtained.

[0137] The obtained compound (B3) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.38-4.19(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-84.22(32F), -86.40(4F), -124.30(4F), -130.08(16F)

[0138] [Example 19] Compound (C1) represented by the above formula (C1) (in formula (C1), mc1 indicating the average degree of polymerization is 3.4, and nc1 indicating the average degree of polymerization is 3.4) was obtained by the method shown below. First, a compound represented by the following formula (16) was synthesized by the method shown below. Compound (16) represented by the following formula (16) was synthesized by reacting compound (11) shown in Example 1 with 2-(4-chlorobutoxy)tetrahydropyran and then oxidizing the double bond with m-chloroperbenzoic acid.

[0139] [ka]

[0140] The same operation as in Example 10 was performed except that compound (16) (7.67 g) represented by formula (16) was used instead of compound (12) represented by formula (12) used in Example 10, to obtain 16.9 g of compound (C1).

[0141] The obtained compound (C1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.68-1.75(4H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0142] [Example 20] Compound (C1) represented by the above formula (C1) (in formula (C1), mc1 indicating the average degree of polymerization is 7.8, and nc1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 19, HOCH2CF2O(CF2CF2O) g (CF2O)h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 19 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.5 g of compound (C1).

[0143] The obtained compound (C1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.68-1.75(4H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0144] [Example 21] Compound (D1) represented by the above formula (D1) (in formula (D1), md1 indicating the average degree of polymerization is 3.4, and nd1 indicating the average degree of polymerization is 3.4) was obtained by the method shown below. First, compound (17) represented by the following formula (17) was synthesized by the method shown below. Compound (17) represented by the following formula (17) was synthesized by reacting compound (11) shown in Example 1 with 2-(6-chlorohexyloxy)tetrahydropyran and then oxidizing the double bond with m-chloroperbenzoic acid.

[0145] [ka]

[0146] The same operation as in Example 10 was performed except that compound (17) (8.28 g) represented by formula (17) was used instead of compound (12) represented by formula (12) used in Example 10, to obtain 17.3 g of compound (D1).

[0147] The obtained compound (D1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.46-1.62(8H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0148] [Example 22] Compound (D1) represented by the above formula (D1) (in formula (D1), md1 indicating the average degree of polymerization is 7.8, and nd1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 21, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 21 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 17.8 g of compound (D1).

[0149] The obtained compound (D1)1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.46-1.62(8H), 3.40-4.20(35H), 5.10(1H), 5.25(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0150] [Example 23] Compound (E1) represented by the above formula (E1) (in formula (E1), me1 indicating the average degree of polymerization is 3.4, and ne1 indicating the average degree of polymerization is 3.4) was obtained by the method shown below. First, compound (19) represented by the following formula (19) was synthesized by the method shown below. After 3-buten-1-ol was reacted with epibromohydrin, the epoxy was hydrolyzed under acidic conditions to synthesize compound (18) represented by the following formula (18). The primary hydroxyl group of the obtained compound (18) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (19) represented by the following formula (19).

[0151] [ka]

[0152] The same operation as in Example 1 was performed except that compound (19) (7.39 g) represented by formula (19) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 16.9 g of compound (E1).

[0153] The obtained compound (E1) 1 H-NMR and 19F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 2.34(2H), 3.40-4.20(35H), 4.98(1H), 5.05(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0154] [Example 24] Compound (E1) represented by the above formula (E1) (in formula (E1), me1 indicating the average degree of polymerization is 7.8, and ne1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 23, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 23 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 15.7 g of compound (E1) was obtained.

[0155] The obtained compound (E1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 2.34(2H), 3.40-4.20(35H), 4.98(1H), 5.05(1H), 5.82(1H) 19F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0156] [Example 25] Compound (F1) represented by the above formula (F1) (in formula (F1), mf1 indicating the average degree of polymerization is 3.4, and nf1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (21) represented by the following formula (21) was synthesized by the method shown below. After 4-penten-1-ol was reacted with epibromohydrin, the epoxy was hydrolyzed under acidic conditions to synthesize compound (20) represented by the following formula (20). The primary hydroxyl group of the obtained compound (20) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (21) represented by the following formula (21).

[0157] [ka]

[0158] The same operation as in Example 1 was performed except that compound (21) (7.81 g) represented by formula (21) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.1 g of compound (F1).

[0159] The obtained compound (F1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.67(2H), 1.75(2H), 2.15(2H), 3.40-4.20(35H), 4.97(1H), 5.03(1H), 5.82(1H) 19F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0160] [Example 26] Compound (F1) represented by the above formula (F1) (in formula (F1), mf1 indicating the average degree of polymerization is 7.8, and nf1 indicating the average degree of polymerization is 7.8) was obtained by the method shown below. In Example 25, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 25 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 17.7 g of compound (F1) was obtained.

[0161] The obtained compound (F1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.67(2H), 1.75(2H), 2.15(2H), 3.40-4.20(35H), 4.97(1H), 5.03(1H), 5.82(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0162] [Example 27] Compound (G1) represented by the above formula (G1) (in formula (G1), mg1 indicating the average degree of polymerization is 3.4, and ng1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (23) represented by the following formula (23) was synthesized by the method shown below. Propargyl alcohol was reacted with epibromohydrin, and then epoxy was hydrolyzed under acidic conditions to synthesize compound (22) represented by the following formula (22). The primary hydroxyl group of the obtained compound (22) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (23) represented by the following formula (23).

[0163] [ka]

[0164] The same operation as in Example 1 was performed except that compound (23) (6.91 g) represented by formula (23) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 16.7 g of compound (G1).

[0165] The obtained compound (G1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 2.48(1H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0166] [Example 28] Compound (G1) represented by the above formula (G1) (in formula (G1), mg1 indicating the average degree of polymerization is 7.8, and ng1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 27, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 27 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.2 g of compound (G1).

[0167] The obtained compound (G1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 2.48(1H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0168] [Example 29] A compound (H1) represented by the above formula (H1) (in formula (H1), mh1 indicating the average degree of polymerization is 3.4, and nh1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (25) represented by the following formula (25) was synthesized by the method shown below. After 4-pentyn-1-ol was reacted with epibromohydrin, the epoxy was hydrolyzed under acidic conditions to synthesize compound (24) represented by the following formula (24). The primary hydroxyl group of the obtained compound (24) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (25) represented by the following formula (25).

[0169] [ka]

[0170] The same operation as in Example 1 was performed, except that compound (25) (7.75 g) represented by formula (25) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.1 g of compound (H1).

[0171] The obtained compound (H1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75-1.78(4H), 2.00(1H), 2.30(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0172] [Example 30] A compound (H1) represented by the above formula (H1) (in formula (H1), mh1 indicating the average degree of polymerization is 7.8, and nh1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 29, HOCH2CF2O(CF2CF2O) g(CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 29 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.5 g of compound (H1).

[0173] The obtained compound (H1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75-1.78(4H), 2.00(1H), 2.30(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0174] [Example 31] Compound (I1) represented by the above formula (I1) (in formula (I1), mi1 indicating the average degree of polymerization is 3.4, and ni1 indicating the average degree of polymerization is 3.4) was obtained by the method shown below. First, compound (27) represented by the following formula (27) was synthesized by the method shown below. After reacting 2-thiopheneethanol with epibromohydrin, epoxy was hydrolyzed under acidic conditions to synthesize compound (26) represented by the following formula (26). The primary hydroxyl group of the obtained compound (26) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (27) represented by the following formula (27).

[0175] [ka]

[0176] The same operation as in Example 1 was performed except that compound (27) (9.07 g) represented by formula (27) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.7 g of compound (I1).

[0177] The obtained compound (I1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.07(2H), 3.40-4.20(35H), 6.90(2H), 7.23(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0178] [Example 32] Compound (I1) represented by the above formula (I1) (in formula (I1), mi1 indicating the average degree of polymerization is 7.8, and ni1 indicating the average degree of polymerization is 7.8) was obtained by the method shown below. In Example 31, HOCH2CF2O(CF2CF2O)g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 31 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 15.4 g of compound (I1).

[0179] The obtained compound (I1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.07(2H), 3.40-4.20(35H), 6.90(2H), 7.23(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0180] [Example 33] A compound (J1) represented by the above formula (J1) (in formula (J1), mj1 indicating the average degree of polymerization is 3.4, and nj1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (29) represented by the following formula (29) was synthesized by the method shown below. After reacting 1-methylpyrazole-5-methanol with epibromohydrin, the epoxy was hydrolyzed under acidic conditions to synthesize compound (28) represented by the following formula (28). The primary hydroxyl group of the obtained compound (28) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (29) represented by the following formula (29).

[0181] [ka]

[0182] The same operation as in Example 1 was performed, except that compound (29) (8.59 g) represented by formula (29) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.5 g of compound (J1).

[0183] The obtained compound (J1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(38H), 6.20(1H), 7.31(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0184] [Example 34] A compound (J1) represented by the above formula (J1) (in formula (J1), mj1 indicating the average degree of polymerization is 7.8, and nj1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 33, HOCH2CF2O(CF2CF2O)g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 33 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 7.8, and h indicating the average degree of polymerization is 7.8) was used, to obtain 15.8 g of compound (J1).

[0185] The obtained compound (J1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(38H), 6.20(1H), 7.31(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0186] [Example 35] A compound (K1) represented by the above formula (K1) (in formula (K1), mk1 indicating the average degree of polymerization is 3.4, and nk1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (30) represented by the following formula (30) was synthesized by the following method: 4-methoxyphenol was reacted with allyl glycidyl ether, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize compound (30) represented by the following formula (30).

[0187] [ka]

[0188] The same operation as in Example 1 was performed, except that the compound (10) represented by formula (10) used in Example 1 was replaced with the compound (30) represented by formula (30) (7.63 g), to obtain 17.7 g of compound (K1).

[0189] The obtained compound (K1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(36H), 6.85(4H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0190] [Example 36] A compound (K1) represented by the above formula (K1) (in formula (K1), mk1 indicating the average degree of polymerization is 7.8, and nk1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 35, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 35 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.1 g of compound (K1).

[0191] The obtained compound (K1) 1 H-NMR and 19F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(36H), 6.85(4H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0192] [Example 37] A compound (L1) represented by the above formula (L1) (in formula (L1), ml1 indicating the average degree of polymerization is 3.4, and nl1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (31) represented by the following formula (31) was synthesized by the following method: 3-cyanophenol was reacted with allyl glycidyl ether, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize compound (31) represented by the following formula (31).

[0193] [ka]

[0194] The same operation as in Example 1 was performed, except that compound (31) (7.48 g) represented by formula (31) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.6 g of compound (L1).

[0195] The obtained compound (L1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(33H), 7.28-7.34(3H), 7.50(1H) 19F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0196] [Example 38] A compound (L1) represented by the above formula (L1) (in formula (L1), ml1 indicating the average degree of polymerization is 7.8, and nl1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 37, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 37 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 15.2 g of compound (L1).

[0197] The obtained compound (L1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(33H), 7.28-7.34(3H), 7.50(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0198] [Example 39] A compound (M1) represented by the above formula (M1) (in formula (M1), mm1 indicating the average degree of polymerization is 3.4, and nm1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (33) represented by the following formula (33) was synthesized by the method shown below. After 3-cyanopropanol was reacted with epibromohydrin, the epoxy was hydrolyzed under acidic conditions to synthesize compound (32) represented by the following formula (32). The primary hydroxyl group of the obtained compound (32) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (33) represented by the following formula (33).

[0199] [ka]

[0200] The same operation as in Example 1 was performed except that compound (33) (7.78 g) represented by formula (33) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.1 g of compound (M1).

[0201] The obtained compound (M1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 1.88(2H), 2.54(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0202] [Example 40] A compound (M1) represented by the above formula (M1) (in formula (M1), mm1 indicating the average degree of polymerization is 7.8, and nm1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 39, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 39 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 7.8, and h indicating the average degree of polymerization is 7.8) was used, and 16.2 g of compound (M1) was obtained.

[0203] The obtained compound (M1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 1.88(2H), 2.54(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0204] [Example 41] Compound (N1) represented by the above formula (N1) (in formula (N1), mn1 indicating the average degree of polymerization is 3.4, and nn1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (35) represented by the following formula (35) was synthesized by the method shown below. After 4-cyanobutanol was reacted with epibromohydrin, the epoxy was hydrolyzed under acidic conditions to synthesize compound (34) represented by the following formula (34). The primary hydroxyl group of the obtained compound (34) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (35) represented by the following formula (35).

[0205] [ka]

[0206] The same operation as in Example 1 was performed except that compound (35) (8.20 g) represented by formula (35) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.3 g of compound (N1).

[0207] The obtained compound (N1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(6H), 2.54(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0208] [Example 42] Compound (N1) represented by the above formula (N1) (in formula (N1), mn1 indicating the average degree of polymerization is 7.8, and nn1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 41, HOCH2CF2O(CF2CF2O) g (CF2O)h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 41 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 15.4 g of compound (N1) was obtained.

[0209] The obtained compound (N1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(6H), 2.54(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0210] [Example 43] Compound (O1) represented by the above formula (O1) (in formula (O1), mo1 indicating the average degree of polymerization is 3.4, and no1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (36) represented by the following formula (36) was synthesized by the method shown below. After protecting the primary hydroxyl group of 3-methoxy-1,2-propanediol with a t-butyldimethylsilyl group, the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (36) represented by the following formula (36).

[0211] [ka]

[0212] The same operation as in Example 1 was performed except that compound (36) (6.19 g) represented by formula (36) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 16.4 g of compound (O1).

[0213] The obtained compound (O1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR(acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(36H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0214] [Example 44] Compound (O1) represented by the above formula (O1) (in formula (O1), mo1 indicating the average degree of polymerization is 7.8, and no1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 43, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 43 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 16.1 g of compound (O1) was obtained.

[0215] The obtained compound (O1)1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR(acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(36H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0216] [Example 45] A compound (P1) represented by the above formula (P1) (in formula (P1), mp1 indicating the average degree of polymerization is 3.4, and np1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (37) represented by the following formula (37) was synthesized by the method shown below. Compound (11) shown in Example 1 was reacted with propyl bromide, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize compound (37) represented by the following formula (37).

[0217] [ka]

[0218] The same operation as in Example 1 was performed except that compound (37) (7.03 g) represented by formula (37) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 16.8 g of compound (P1).

[0219] The obtained compound (P1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=0.84(3H), 1.55(2H), 1.75(2H), 3.40-4.20(35H) 19F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0220] [Example 46] A compound (P1) represented by the above formula (P1) (in formula (P1), mp1 indicating the average degree of polymerization is 7.8, and np1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 45, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 45 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 14.4 g of compound (P1) was obtained.

[0221] The obtained compound (P1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=0.84(3H), 1.55(2H), 1.75(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0222] [Example 47] Compound (Q1) represented by the above formula (Q1) (in formula (Q1), mq1 indicating the average degree of polymerization is 3.4, and nq1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (38) represented by the following formula (38) was synthesized by the following method: 2,2,2-trifluoroethanol was reacted with allyl glycidyl ether, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize compound (38) represented by the following formula (38).

[0223] [ka]

[0224] The same operation as in Example 1 was performed, except that compound (38) (6.91 g) represented by formula (38) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.3 g of compound (Q1).

[0225] The obtained compound (Q1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -75.22(3F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0226] [Example 48] Compound (Q1) represented by the above formula (Q1) (in formula (Q1), mq1 indicating the average degree of polymerization is 7.8, and nq1 indicating the average degree of polymerization is 7.8) was obtained by the method shown below. In Example 47, HOCH2CF2O(CF2CF2O) g (CF2O) hInstead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 47 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.3 g of compound (Q1).

[0227] The obtained compound (Q1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -75.22(3F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0228] [Example 49] A compound (R1) represented by the above formula (R1) (in formula (R1), mr1 indicating the average degree of polymerization is 3.4, and nr1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (39) represented by the following formula (39) was synthesized by the following method: 2,2,3,3,3-pentafluoro-1-propanol was reacted with allyl glycidyl ether, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize compound (39) represented by the following formula (39).

[0229] [ka]

[0230] The same operation as in Example 1 was performed except that compound (39) (8.41 g) represented by formula (39) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 18.0 g of compound (R1).

[0231] The obtained compound (R1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -84.40(3F), -89.16~-91.14(13.6F), -124.36(2F)

[0232] [Example 50] A compound (R1) represented by the above formula (R1) (in formula (R1), mr1 indicating the average degree of polymerization is 7.8, and nr1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 49, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 49 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 15.7 g of compound (R1).

[0233] The obtained compound (R1) 1 H-NMR and 19F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(35H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -84.40(3F), -89.16~-91.14(31.2F), -124.36(2F)

[0234] [Example 51] A compound (S1) represented by the above formula (S1) (in formula (S1), ms1 indicating the average degree of polymerization is 3.4, and ns1 indicating the average degree of polymerization is 3.4) was obtained by the method described below. First, compound (40) represented by the following formula (40) was synthesized by the method shown below. Compound (11) shown in Example 1 was reacted with 2-bromoethyl methyl ether, and then the double bond was oxidized using m-chloroperbenzoic acid to synthesize compound (40) represented by the following formula (40).

[0235] [ka]

[0236] The same operation as in Example 1 was performed, except that compound (40) (7.51 g) represented by formula (40) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.6 g of compound (S1).

[0237] The obtained compound (S1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.31(3H), 3.40-4.20(37H) 19F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0238] [Example 52] A compound (S1) represented by the above formula (S1) (in formula (S1), ms1 indicating the average degree of polymerization is 7.8, and ns1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 51, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 51 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, and 16.1 g of compound (S1) was obtained.

[0239] The obtained compound (S1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.31(3H), 3.40-4.20(37H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0240] [Example 53] A compound (T1) represented by the above formula (T1) (in formula (T1), mt1 indicating the average degree of polymerization is 3.4, and nt1 indicating the average degree of polymerization is 3.4) was obtained by the method shown below. First, compound (42) represented by the following formula (42) was synthesized by the method shown below. Ethylene glycol monoallyl ether was reacted with epibromohydrin, and then epoxy was hydrolyzed under acidic conditions to synthesize compound (41) represented by the following formula (41). The primary hydroxyl group of the obtained compound (41) was protected with a t-butyldimethylsilyl group, and then the secondary hydroxyl group was protected with a methoxymethyl group, and the t-butyldimethylsilyl group was removed from the obtained compound. Finally, epibromohydrin was reacted with the generated primary hydroxyl group to synthesize compound (42) represented by the following formula (42).

[0241] [ka]

[0242] The same operation as in Example 1 was performed except that compound (42) (8.29 g) represented by formula (42) was used instead of compound (10) represented by formula (10) used in Example 1, to obtain 17.3 g of compound (T1).

[0243] The obtained compound (T1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(39H), 5.10(1H), 5.26(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(6.8F), -78.48(2F), -80.66(2F), -89.16~-91.14(13.6F)

[0244] [Example 54] A compound (T1) represented by the above formula (T1) (in formula (T1), mt1 indicating the average degree of polymerization is 7.8, and nt1 indicating the average degree of polymerization is 7.8) was obtained by the method described below. In Example 53, HOCH2CF2O(CF2CF2O) g (CF2O) h Instead of the fluoropolyether (number average molecular weight 800, molecular weight distribution 1.1) represented by CF2CH2OH (wherein g indicating the average degree of polymerization is 3.4, and h indicating the average degree of polymerization is 3.4), HOCH2CF2O(CF2CF2O) g (CF2O) h The same procedure as in Example 53 was carried out, except that fluoropolyether (number average molecular weight 1600, molecular weight distribution 1.1) (40.0 g) represented by CF2CH2OH (wherein g, which indicates the average degree of polymerization, is 7.8, and h, which indicates the average degree of polymerization, is 7.8) was used, to obtain 16.0 g of compound (T1).

[0245] The obtained compound (T1) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-d6): δ[ppm]=1.75(2H), 3.40-4.20(39H), 5.10(1H), 5.26(1H), 5.91(1H) 19 F-NMR (acetone-d6): δ[ppm]=-51.99~-55.72(15.6F), -78.48(2F), -80.66(2F), -89.16~-91.14(31.2F)

[0246] [Comparative Examples 1 to 4] Compound (AA) represented by the following formula (AA) was synthesized by the method described in Patent Document 5.

[0247] [ka] (In formula (AA), maa and naa, which indicate the average degree of polymerization, are both 3.4 in Comparative Example 1, 6.2 in Comparative Example 2, 7.8 in Comparative Example 3, and 10 in Comparative Example 4.)

[0248] [Comparative Examples 5 to 8] Compound (BB) represented by the following formula (BB) was synthesized by the method described in Patent Document 4.

[0249] [ka] (In formula (BB), mbb and nbb, which indicate the average degree of polymerization, are both 3.4 in Comparative Example 5, 6.2 in Comparative Example 6, 7.8 in Comparative Example 7, and 10 in Comparative Example 8.)

[0250] [Comparative Example 9 and Comparative Example 10] A compound (CC) represented by the following formula (CC) was synthesized by the method described in Patent Document 7.

[0251] [ka] (In formula (CC), mcc and ncc, which indicate the average degree of polymerization, are both 3.4 in Comparative Example 9, and 7.8 in Comparative Example 10.)

[0252] [Comparative Example 11 and Comparative Example 12] Compound (DD) represented by the following formula (DD) was synthesized by the method described in Patent Document 7.

[0253] [ka] (In formula (DD), mdd and ndd, which indicate the average degree of polymerization, are both 3.4 in Comparative Example 11, and 7.8 in Comparative Example 12.)

[0254] [Comparative Example 13 and Comparative Example 14] A compound (EE) represented by the following formula (EE) was synthesized by the method described in Patent Document 6.

[0255] [ka] (In formula (EE), mee and nee, which indicate the average degree of polymerization, are both 3.4 in Comparative Example 13, and are both 7.8 in Comparative Example 14.)

[0256] When the compounds obtained in the above Examples 1 to 54 and Comparative Examples 1 to 14 are applied to the formula (1), R 1 ~R 3 , (O(CH2) a ) b The structures of [A] and [B] are shown in Table 1 below.

[0257] [Table 1]

[0258] Next, a lubricant layer-forming solution was prepared using the compounds obtained in Examples 1 to 54 and Comparative Examples 1 to 14 by the method described below. Then, using the obtained lubricant layer-forming solution, a lubricant layer of a magnetic recording medium was formed by the method described below, and the magnetic recording media of Examples 1 to 54 and Comparative Examples 1 to 14 were obtained.

[0259] [Lubricant layer forming solution] The compounds obtained in Examples 1 to 54 and Comparative Examples 1 to 14 were each dissolved in a fluorine-based solvent, Vertrel (registered trademark) XF (product name, manufactured by Mitsui DuPont Fluorochemicals Co., Ltd.), and diluted with Vertrel XF so that the film thickness when applied onto the protective layer would be 8.5 Å to 10 Å, to prepare a lubricating layer-forming solution having a compound concentration of 0.001% by mass to 0.01% by mass.

[0260] [Magnetic recording media] A magnetic recording medium was prepared by sequentially providing an adhesive layer, a soft magnetic layer, a first underlayer, a second underlayer, a magnetic layer, and a protective layer on a substrate having a diameter of 65 mm. The protective layer was made of nitrogenated carbon. The lubricant layer forming solutions of Examples 1 to 54 and Comparative Examples 1 to 14 were applied by dipping onto the protective layer of the magnetic recording medium on which each layer up to the protective layer had been formed. Thereafter, the magnetic recording medium coated with the lubricant layer-forming solution was placed in a thermostatic chamber at 120° C. and subjected to a heat treatment for 10 minutes, thereby forming a lubricant layer on the protective layer and obtaining a magnetic recording medium. The magnetic recording media thus obtained in Examples 1 to 54 and Comparative Examples 1 to 14 were evaluated by the following methods: thickness of the lubricating layer, adhesion (bond ratio) between the lubricating layer and the protective layer, pickup characteristics test, and spin-off characteristics test. The results are shown in Tables 2 to 5.

[0261] [Lubrication layer thickness measurement] The peak height of the CF vibrational stretching of the lubricating layer was measured using an FT-IR (product name: Nicolet iS50, manufactured by Thermo Fisher Scientific Co., Ltd.). Next, the film thickness of the lubricating layer was calculated from the measured value of the peak height of the CF vibrational stretching of the lubricating layer using a correlation equation obtained by the method described later.

[0262] [How to calculate the correlation equation] A lubricating layer was formed with a thickness of 6 to 20 Å (in 2 Å increments) on the surface of a disk having an adhesive layer, a soft magnetic layer, a first underlayer, a second underlayer, a magnetic layer, and a protective layer formed in that order on a substrate with a diameter of 65 mm. Then, for each disk on which a lubricating layer was formed, the increment in film thickness from the disk surface on which a lubricating layer was not formed was measured using an ellipsometer, and this was taken as the film thickness of the lubricating layer. In addition, for each disk on which a lubricating layer was formed, the peak height in the CF vibration stretching was measured using FT-IR. A correlation equation was then determined between the peak height obtained by FT-IR and the film thickness of the lubricant layer obtained by using an ellipsometer.

[0263] [Measurement of adhesion (bond ratio) between lubricating layer and protective layer] The magnetic recording medium on which the lubricating layer was formed was immersed in a solvent, Vertrel XF, for 10 minutes and then pulled up for cleaning. The magnetic recording medium was immersed in the solvent at a speed of 10 mm / sec and pulled up at a speed of 1.2 mm / sec. The thickness of the lubricating layer was then measured using the same method as that used for measuring the thickness of the lubricating layer before cleaning. The thickness of the lubricant layer before cleaning was defined as α, and the thickness of the lubricant layer after cleaning (solvent immersion) was defined as β, and the bonding rate of the lubricant was calculated from the ratio of α to β ((β / α)×100(%)). Using the calculated bonding rate, the adhesion between the lubricant layer and the protective layer was evaluated according to the following evaluation criteria. The bond ratio can be used as an index of the bonding strength between the lubricant layer and the protective layer. If the adhesion between the lubricant layer and the protective layer is poor, some of the fluorine-containing ether compounds contained in the lubricant layer will dissolve into the Vertrel XF and be washed away. This reduces the thickness of the lubricant layer after cleaning, and the bond ratio decreases.

[0264] "Adhesion (bond rate) evaluation criteria" A: Bond rate 75% or more B: Bond rate 70% to 74% C: Bond rate 50%~69% D: Bond rate 49% or less

[0265] [Pickup characteristic test] The magnetic recording medium and the magnetic head were mounted on a spin stand, and the magnetic head was floated at a fixed point for 10 minutes under reduced pressure (approximately 250 torr) at room temperature. The surface of the magnetic head facing the magnetic recording medium was then analyzed using an ESCA (Electron Spectroscopy for Chemical Analysis) analyzer. The intensity of the fluorine-derived peak (signal intensity (au)) obtained by the ESCA analysis indicates the amount of lubricant attached to the magnetic head. The pickup characteristics were evaluated using the obtained signal intensity according to the following evaluation criteria.

[0266] "Evaluation criteria for pickup characteristics" A: Signal strength 160 or less (very little adhesion) B: Signal strength 161-300 (low adhesion) C: Signal strength 301-1000 (high adhesion) D: Signal strength 1001 or more (very heavy adhesion)

[0267] [Spin-off characteristic test] The magnetic recording medium was mounted on a spin stand and rotated at a rotation speed of 10,000 rpm for 72 hours in an environment of 80°C. Before and after this operation, the thickness of the lubricating layer was measured by FT-IR at a position of a radius of 20 mm from the center of the magnetic recording medium, and the thickness reduction rate of the lubricating layer before and after the test was calculated. Using the calculated thickness reduction rate, the spin-off characteristics were evaluated according to the following evaluation criteria.

[0268] "Evaluation criteria for spin-off characteristics" A: Film thickness reduction rate less than 2% B: Film thickness reduction rate is greater than 2% and less than 3% C: Film thickness reduction rate: greater than 3% and less than 9% D: Film thickness reduction rate of 10% or more

[0269] From these results, an overall evaluation was made according to the following evaluation criteria. "comprehensive evaluation" A: The bond rate, pick-up characteristics, and spin-off characteristics are all rated A. B: The bond rate, pick-up characteristics, and spin-off characteristics are rated A or B, with at least one of them being rated B. C: One or more of the evaluations of bond rate, pick-up characteristics, and spin-off characteristics are C, and there is no D. D: At least one of the evaluations of bond rate, pick-up characteristics, and spin-off characteristics is D.

[0270] [Table 2]

[0271] [Table 3]

[0272] [Table 4]

[0273] [Table 5]

[0274] As shown in Tables 2 to 5, the magnetic recording media of Examples 1 to 54 used the fluorine-containing ether compound represented by formula (1), and therefore had a higher bond ratio and better adhesion between the lubricating layer and the protective layer compared to the magnetic recording media of Comparative Examples 1 to 14. Furthermore, as shown in Tables 2 to 5, since the magnetic recording media of Examples 1 to 54 use the fluorine-containing ether compound represented by formula (1), the signal intensity derived from fluorine obtained by ESCA analysis is smaller than that of the magnetic recording media of Comparative Examples 1 to 14, and it is clear that pickup can be suppressed. Furthermore, as shown in Tables 2 to 5, since the magnetic recording media of Examples 1 to 54 use the fluorine-containing ether compound represented by formula (1), the film thickness reduction rate is smaller and spin-off can be suppressed compared to the magnetic recording media of Comparative Examples 1 to 3, 5 to 7, and 9 to 14, which have similar number average molecular weights. In the magnetic recording media of Comparative Examples 1 to 14, when the Comparative Examples using the same fluorine-containing ether compound were compared with each other, it was found that the pick-up characteristics and spin-off characteristics significantly deteriorated as the number average molecular weight decreased. On the other hand, in the magnetic recording media of Examples 1 to 54, even if the number average molecular weight was reduced, no significant deterioration in the pick-up characteristics and spin-off characteristics was observed.

[0275] In Comparative Examples 1 to 4, R represented by formula (4) in formula (1) 3An evaluation test was carried out using compound (AA) where f = 1. Since f = 1 in compound (AA), the structure is stabilized by the regular arrangement of five-membered ring-type intramolecular hydrogen bonds between the ether oxygen atom and the hydroxyl group in formula (4), which reduces the adhesion to the protective layer (bond ratio) and shows a tendency for the pickup characteristics and spin-off characteristics to deteriorate. In addition, when comparing Comparative Examples 1 and 2 related to compound (AA) with Comparative Examples 3 and 4, it was confirmed that Comparative Examples 1 and 2, which have small number average molecular weights, tend to have poor pick-up properties and spin-off properties.

[0276] In Comparative Examples 5 to 8, R in formula (1) 3 is replaced with -O-CH2-CH(OH)-CH2-O-CH2-CH2-OH, and has one secondary hydroxyl group and one primary hydroxyl group. 3 The number of secondary hydroxyl groups is smaller than that of the protective layer, and therefore adhesion to the protective layer is reduced, and the fluorine-containing ether compound that is not in close contact with the protective layer tends to aggregate and adhere to the magnetic head as foreign matter. In addition, when comparing Comparative Examples 5 and 6 related to compound (BB) with Comparative Examples 7 and 8, it was confirmed that Comparative Examples 5 and 6, which have small number average molecular weights, tend to have worsening pick-up characteristics and spin-off characteristics.

[0277] In Comparative Examples 9 to 12, R represented by formula (4) in formula (1) 3 Evaluation tests were carried out using compounds (CC) and (DD) where f = 1. Since f = 1 in compounds (CC) and (DD), the structure is stabilized by the regular arrangement of five-membered ring-type intramolecular hydrogen bonds between the ether oxygen atom and the hydroxyl group in formula (4), and it was confirmed that the adhesion to the protective layer (bond ratio) decreases and the pickup characteristics and spin-off characteristics tend to deteriorate. In addition, when Comparative Example 9 and Comparative Example 10 related to compound (CC) are compared, it is confirmed that Comparative Example 9, which has a small number average molecular weight, has a tendency for the pick-up characteristics and spin-off characteristics to deteriorate. When Comparative Example 11 and Comparative Example 12 related to compound (DD), it is confirmed that Comparative Example 11, which has a small number average molecular weight, has a tendency for the pick-up characteristics and spin-off characteristics to deteriorate.

[0278] In Comparative Examples 13 and 14, the sum of c and d in the -[A]-[B]- structure in formula (1) is 1, and R 3 is replaced by -O-CH2-CH(OH)-CH2-O-CH2-CH2-CH2-OH, and has one secondary hydroxyl group and one primary hydroxyl group. That is, compared with the formula (1) of the present invention, even in the -[A]-[B]- structure, R 3 In the structure of the ferromagnetic layer, a compound (EE) with a small number of secondary hydroxyl groups is used. Therefore, it was confirmed that the adhesion to the protective layer is reduced, and the pick-up characteristics and spin-off characteristics tend to deteriorate.

[0279] When Examples 1 to 3 (compound (A1)) and Comparative Examples 1 to 4 (compound (AA)), Examples 37 to 38 (compound (L1)) and Comparative Examples 9 to 10 (compound (CC)), and Examples 39 to 40 (compound (M1)) and Comparative Examples 11 to 12 (compound (DD)), it is clear that the R 3 It was revealed that by increasing one methylene carbon in the ethylene glycol carbide, the bond ratio was significantly increased, and the pick-up and spin-off properties were significantly improved. These results are believed to be due to the fact that the terminal primary hydroxyl groups of compounds (AA), (CC) and (DD) are not effectively involved in bonding with the active sites on the protective layer, and therefore sufficient adhesion to the protective layer is not obtained. On the other hand, in compounds (A1), (L1) and (M1), R 3 It is presumed that by increasing the number of methylene carbons, the regular five-membered ring arrangement of the ether oxygen atoms and hydroxyl groups in the molecule is disrupted, inhibiting the intramolecular interaction of the hydroxyl groups, resulting in a significant improvement in adhesion to the protective layer. [Industrial Applicability]

[0280] Provided is a fluorine-containing ether compound which has good adhesion to a protective layer, can form a lubricating layer capable of suppressing pick-up and spin-off even when the molecular weight is reduced, and can be suitably used as a material for a lubricant for a magnetic recording medium. [Explanation of symbols]

[0281] 10 magnetic recording medium, 11 substrate, 12 adhesion layer, 13 soft magnetic layer, 14 first underlayer, 15 second underlayer, 16 magnetic layer, 17 protective layer, and 18 lubricating layer.

Claims

1. A fluorine-containing ether compound represented by the following formula (1): R 1 -(O(CH 2 ) a ) b -[A]-[B]-O-CH 2 -R 2 -CH 2 -R 3 (1) (In formula (1), R 1 is any one of an alkyl group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms and having a fluoro or cyano group as a substituent, an organic group having 6 to 12 carbon atoms and having an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms and having an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms, The organic group having 6 to 12 carbon atoms and an aromatic hydrocarbon is one selected from the group consisting of a phenyl group, a methoxyphenyl group, a cyanophenyl group, and a phenethyl group, and the organic group having 3 to 10 carbon atoms and an aromatic heterocycle is one selected from the group consisting of a thienylethyl group and an N-methylpyrazolylmethyl group. a is an integer of 2 to 4, and b is 0 or 1. [A] is represented by the following formula (2). In formula (2), c is 1 or 2. [B] is represented by the following formula (3). In formula (3), d is 0 or 1, and e is an integer of 2 to 4. However, the sum of the values ​​of c in formula (2) and d in formula (3) is 2. R 2 is a perfluoropolyether chain. 3 is expressed by the following formula (4). In formula (4), f is an integer of 2 to 5. 【Chemistry 1】

2. 2. The fluorine-containing ether compound according to claim 1, having a number average molecular weight in the range of 1,000 to 2,300.

3. R in the formula (1) 1 The fluorine-containing ether compound according to claim 1 or 2, wherein is an alkyl group having 1 to 6 carbon atoms.

4. R in the formula (1) 1 3. The fluorine-containing ether compound according to claim 1 or 2, wherein R is an alkyl group having 1 to 6 carbon atoms and having a fluoro group or a cyano group as a substituent.

5. R in the formula (1) 1 is any one of an organic group having 6 to 12 carbon atoms and containing an aromatic hydrocarbon, an organic group having 3 to 10 carbon atoms and containing an aromatic heterocycle, an alkenyl group having 2 to 8 carbon atoms, and an alkynyl group having 3 to 8 carbon atoms; the organic group having 6 to 12 carbon atoms and having an aromatic hydrocarbon is one selected from the group consisting of a phenyl group, a methoxyphenyl group, a cyanophenyl group, and a phenethyl group, 3. The fluorine-containing ether compound according to claim 1, wherein the organic group having 3 to 10 carbon atoms and an aromatic heterocycle is one selected from the group consisting of a thienylethyl group and an N-methylpyrazolylmethyl group.

6. R in the formula (1) 1 is one group selected from the group consisting of a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,2,2,2,2-hexafluoroisopropyl group, a 2-cyanoethyl group, a 3-cyanopropyl group, a 4-cyanobutyl group, a phenyl group, a methoxyphenyl group, a cyanophenyl group, a phenethyl group, a thienylethyl group, an N-methylpyrazolylmethyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, a propargyl group, a 3-butynyl group, and a 4-pentynyl group.

7. R in the formula (1) 2 The fluorine-containing ether compound according to any one of claims 1 to 6, wherein is represented by the following formulas (5) to (8): -CF 2 O-(CF 2 CF 2 O) g -(CF 2 O) h -CF 2 - (5) (In the formula (5), g and h are average degrees of polymerization, g is 3 to 8, and h is 3 to 8.) 2 O-(CF 2 CF 2 O) i -CF 2 - (6) (In formula (6), i is the average degree of polymerization and represents 5 to 13.) -CF 2 CF 2 O-(CF 2 CF 2 CF 2 O) j -CF 2 CF 2 - (7) (In formula (7), j is the average degree of polymerization and represents 3 to 8.) -CF(CF 3 )-(OCF(CF 3 )CF 2 ) k -OCF(CF 3 )- (8) (In formula (8), k is the average degree of polymerization and represents 3 to 8.)

8. The fluorine-containing ether compound according to claim 1, wherein the compound represented by formula (1) is any of compounds represented by the following formulas (A1) to (A3), (B1) to (B3), (L1), and (M1): 【Chemistry 2】 (In formula (A1), ma1 and na1 are average degrees of polymerization, ma1 represents 3 to 8, and na1 represents 3 to 8.) (In formula (A2), na2 is the average degree of polymerization and represents 5 to 13.) (In formula (A3), na3 is the average degree of polymerization and represents 3 to 8.) (In formula (B1), mb1 and nb1 are average degrees of polymerization, mb1 represents 3 to 8, and nb1 represents 3 to 8.) (In formula (B2), nb2 is the average degree of polymerization and represents 5 to 13.) (In formula (B3), nb3 is the average degree of polymerization and represents 3 to 8.) (In formula (L1), ml1 and nl1 are average degrees of polymerization, ml1 represents 3 to 8, and nl1 represents 3 to 8.) (In formula (M1), mm1 and nm1 are average degrees of polymerization, mm1 represents 3 to 8, and nm1 represents 3 to 8.)

9. A lubricant for magnetic recording media, comprising the fluorine-containing ether compound according to any one of claims 1 to 8.

10. A magnetic recording medium comprising at least a magnetic layer, a protective layer and a lubricating layer provided in that order on a substrate, the lubricating layer comprising the fluorine-containing ether compound according to any one of claims 1 to 8.

11. 11. The magnetic recording medium according to claim 10, wherein the average thickness of the lubricating layer is from 0.5 nm to 2.0 nm.

Citation Information

Patent Citations

  • Averaging device for reverse projection value

    JP1979065454A

  • Electron gun structure of cathode-ray tube

    JP1984009837A

  • Fluorine-containing ether compound, lubricant for magnetic recording medium and magnetic recording medium

    JP2018024614A

  • Magnetic recording media

    JP4632144B2

  • Fluorine-containing ether compound, lubricant for magnetic recording medium, and magnetic recording medium

    WO2017145995A1